Amination catalysts, and preparation and use thereof
A catalyst with a high L acid content inorganic support and Group VIII/IB metals addresses imine polymerization issues, enhancing catalytic activity and stability for amination reactions, resulting in improved organic amine production.
Patent Information
- Application Number
- JP2023526287
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-10-30
- Filing Date
- 2021-10-26
- Publication Date
- 2025-12-17
- Estimated Expiration
- 2041-10-26
AI Technical Summary
Existing catalysts for amination reactions suffer from limitations in catalytic activity, reaction conversion, product selectivity, and catalyst stability, particularly due to the presence of hydroxyl groups on the support surface promoting imine polymerization.
A catalyst comprising an inorganic porous support with a high L acid content, containing aluminum and/or silicon, and an active metal component selected from Group VIII and Group IB metals, optionally with a metal promoter, is used for amination reactions, which minimizes imine polymerization and enhances catalytic performance.
The catalyst exhibits improved catalytic activity, reaction conversion, and product selectivity, along with increased catalyst stability, making it more effective in producing organic amines through amination.
Smart Images

Figure 0007787888000001 
Figure 0007787888000002 
Figure 0007787888000003
Abstract
Description
Detailed Description of the Invention
[0001] [Technical Field] This application relates to the field of amination reactions, and in particular to catalysts useful in producing organic amines by catalytic amination, their preparation and use.
[0002] [Background technology] Amines are very important industrial organic compounds and are widely used in various fields (e.g., as solvents, medical intermediates, resin raw materials, textile additives, insecticides, rubber stabilizers, preservatives, and also in cleaning and plastics processing). The three main processes for producing amines are the hydroamination of carbonyl compounds, the hydroamination of alcohols, and the hydrogenation of nitriles. Hydroamination of carbonyl compounds, for example, involves the reaction of acetone, hydrogen, and ammonia to form isopropylamine. Examples of alcohol hydroamination include the hydroamination of ethanol with ammonia in the presence of hydrogen to form ethylamine, the hydroamination of isopropanol with ammonia in the presence of hydrogen to form isopropylamine, the hydroamination of butanol with ammonia in the presence of hydrogen to form butylamine, and the hydroamination of hexanediol with ammonia in the presence of hydrogen to form hexanediamine. Examples of nitrile hydrogenation include the hydrogenation of acetonitrile to ethylamine and the hydrogenation of adiponitrile to hexanediamine.
[0003] Chinese Patent Application No. CN102658162A discloses a catalyst for synthesizing ethyleneamines and a process for producing the same. The catalyst consists of three components: a main active component, a cofactor, and an amination support. The main active component is one or more elements selected from Ni and Co, accounting for 1-40% of the total weight of the catalyst. The cofactor is one or more elements selected from the group consisting of Fe, Cu, Ru, Re, K, Zn, and B and their oxides, accounting for 0.1-20% of the total weight of the catalyst. The amination support is obtained by amination of one or more supports selected from the group consisting of SiO2 and Al2O3. The amination treatment involves contacting the support with an ammonia source at a temperature of 150-400°C for 0.5-15 hours. The inventors of the present application have found that there are a large number of hydroxyl groups on the surface of the SiO2 or Al2O3 support, and an acidic environment exists on the surface of the support, which promotes the polymerization of the intermediate product imine; however, when the support in the catalyst is aminated, the large number of hydroxyl groups on the surface of the support are converted into amine groups, so that the support exhibits an alkaline environment, which reduces the possibility of imine polymerization and improves the activity, selectivity and stability of the catalyst, and therefore the material of the support has a close relationship with the activity of the catalyst.
[0004] In the prior art, it is generally accepted that the alkalinity of catalysts for producing amines by amination of alcohols is more favorable for improving the activity and selectivity of the catalyst, and the activity of existing catalysts for amination reactions has a large promotion space.
[0005] Summary of the Invention It is an object of the present application to provide a catalyst useful for producing organic amines by catalytic amination, its preparation and use, which exhibits improved performance (e.g., at least one of improved catalytic activity, improved reaction conversion, improved product selectivity, and improved catalyst stability) when used for the amination reaction.
[0006] To achieve the above-mentioned object, in one aspect, the present application provides a catalyst useful for producing an organic amine by catalytic amination, comprising an inorganic porous support containing aluminum and / or silicon, and an active metal component supported on the support, wherein the active metal component comprises at least one metal selected from Group VIII metals and Group IB metals, and the support has an L acid content of 85% or more relative to the sum of the L acid content and the B acid content.
[0007] Preferably, the support comprises a matrix and a doping element, the matrix being selected from alumina, silica, molecular sieve, diatomaceous earth, aluminosilicate, or a combination thereof, and the doping element being a non-metallic element.
[0008] Preferably, the catalyst further comprises a metal promoter supported on the support, the metal promoter comprising at least one metal selected from the group consisting of Group VIB, Group VIIB, Group IB, Group IIB and the Lanthanides, or a combination of at least one Group IIA metal, at least one Group IIB metal and at least one Group VA metal.
[0009] In another aspect, there is provided a method for producing the catalyst of the present application, comprising the following steps 1) to 3): 1) providing an inorganic porous support containing aluminum and / or silicon, the support having an L acid content of 85% or more relative to the total of the L acid content and the B acid content; 2) supporting the active metal component and, optionally, the metal cocatalyst on the support; and 3) subjecting the material obtained in step 2) to a heat treatment and optionally a reduction treatment to obtain said catalyst.
[0010] In yet another aspect, the present application provides a process for producing an organic amine, comprising the step of contacting an amination feedstock and an aminating agent with a catalyst for an amination reaction according to the present application in the presence of hydrogen to obtain an organic amine, wherein the amination feedstock is selected from the group consisting of an alcohol, a ketone, an alcoholamine, an aldehyde, and combinations thereof; and the aminating agent is selected from the group consisting of ammonia, a primary amine, a secondary amine, and combinations thereof.
[0011] When the catalysts of the present application are used to produce organic amines by catalytic amination, they exhibit improved performance, particularly improved catalytic activity, reaction conversion, product selectivity and / or catalyst stability.
[0012] Other features and advantages of the present application are explained in detail in the detailed description that follows.
[0013] Detailed Description of the Invention The present application will be described in more detail below with reference to specific embodiments thereof. It should be noted that the specific embodiments of the present application are provided for illustrative purposes only and are not intended to be limiting in any way.
[0014] Any specific numerical value, including the endpoints of a numerical range, set forth in the context of this application should not be limited to that exact value, but should also be interpreted as encompassing all values near that exact value (e.g., all values within ±5% of that exact value). Furthermore, with respect to any numerical range described herein, any combination between the endpoints of the range, between each endpoint and any specific value within the range, or between any two specific values within the range, can be made to provide one or more new numerical ranges, and such new numerical ranges should also be considered to be specifically set forth in this application.
[0015] Unless otherwise specified, terms used herein have the same meaning as commonly understood by one of ordinary skill in the art; if a term is defined herein and that definition differs from the common understanding in the art, the definition provided herein shall prevail.
[0016] In the present application, the ratio of the L acid content of the catalyst support to the total of the L acid content and the B acid content is measured by pyridine probe adsorption analysis.
[0017] In this application, the ammonia adsorption capacity of the support and catalyst is measured by the NH3-TPD test, and the ammonia adsorption capacity is expressed as the measured amount of ammonia desorption.
[0018] In this application, the specific surface area, pore volume and proportion of pores with different pore diameters of the support are measured by nitrogen adsorption-desorption method in accordance with GB / T6609.35-2009.
[0019] As used herein, the term "C2-C20" means having 2 to 20 carbon atoms (e.g., 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, or 20 carbon atoms). Similarly, the term "C1-C12" means having 1 to 12 carbon atoms.
[0020] In this application, the particle size of the active metal component and the metal promoter is measured by XRD analysis.
[0021] In this application, the isoelectric point of the carrier is measured by means of a particle size potentiometer.
[0022] In this application, pressures given are gauge pressures unless otherwise specified.
[0023] In the context of this application, in addition to the matters explicitly mentioned, any matter or matters not mentioned shall be deemed to be the same as those known in the art without any modifications. Furthermore, any of the embodiments described herein can be freely combined with one or more other embodiments described herein. Any technical solution or idea obtained in this way shall be considered to be part of the original disclosure or original description of this application, and shall not be considered to be new matter not disclosed or anticipated herein, unless it is obvious to a person skilled in the art that such a combination is obviously unreasonable.
[0024] All patent and non-patent literature cited herein, including but not limited to textbooks and journal articles, is hereby incorporated by reference in its entirety.
[0025] As described above, in a first aspect, the present application provides a catalyst useful for producing organic amines by catalytic amination, comprising an inorganic porous support containing aluminum and / or silicon and an active metal component supported on the support, wherein the active metal component comprises at least one metal selected from Group VIII metals and Group IB metals, and the support has an L acid content of 85% or more relative to the sum of the L acid content and the B acid content.
[0026] According to the present application, the Group VIII metal may be, for example, cobalt, nickel, or palladium, and the Group IB metal may be, for example, copper. In a preferred embodiment, the metal in the active metal component is selected from cobalt, nickel, palladium, copper, or a combination thereof, more preferably selected from cobalt, nickel, or a combination thereof.
[0027] In the catalyst of the present application, a Group IB metal (e.g., copper, etc.) can be used alone as the active metal component, in which case it is typically used in a relatively large amount; a Group IB metal can also be used in combination with a Group VIII metal, in which case it is typically used in a relatively small amount. When used in combination with a Group VIII metal (e.g., cobalt, nickel, palladium, etc.), the Group IB metal is generally referred to herein as a metal cocatalyst.
[0028] In a preferred embodiment, the L acid content of the carrier is 88% or more, more preferably 90% or more, particularly preferably 92% or more, based on the total of the L acid content and the B acid content.
[0029] In a preferred embodiment, the support comprises a matrix and a doping element, the matrix being selected from alumina, silica, molecular sieve, diatomaceous earth, aluminosilicate, or a combination thereof, and the doping element is a non-metallic element, preferably at least one selected from the group consisting of Group IIIA, Group VA, Group VIA, and Group VIIA non-metallic elements excluding chlorine, more preferably at least one selected from the group consisting of boron, fluorine, phosphorus, sulfur, and selenium.More preferably, the doping element in the support is derived from a non-metallic acid radical ion, and the non-metallic acid radical ion is preferably at least one selected from the group consisting of borate ions, fluoride ions, phosphate ions, sulfate ions, and selenate ions.
[0030] In a preferred embodiment, the carrier has at least one of the following characteristics: The ratio of the pore volume of pores having a pore diameter in the range of 7 to 27 nm to the pore volume of the support is more than 65%, preferably 70 to 90%, and the ratio of the pore volume of pores having a pore diameter of less than 7 nm to the pore volume of the support is 0 to 10%, preferably 0 to 8%, and when the support has the above-mentioned pore diameter distribution, it is preferable because it enhances the surface diffusivity of the catalyst and improves the activity and product selectivity of the catalyst; the ratio of the pore volume of pores having a pore diameter of less than 7.5 nm to the pore volume of the support is less than 20%, preferably 5 to 17%, the ratio of the pore volume of pores having a pore diameter of less than 9 nm to the pore volume of the support is less than 40%, the ratio of the pore volume of pores having a pore diameter of more than 27 nm to the pore volume of the support is less than 5%, preferably 0.5 to 5%, preferably the ratio of the pore volume of pores having a pore diameter of 7.5 nm or more but less than 9 nm to the pore volume of the support is 5 to 17%, and the ratio of the pore volume of pores having a pore diameter of 9 nm or more but 27 nm to the pore volume of the support is 61 to 89.5%, and when the support has the above-mentioned pore diameter distribution, it is preferable to enhance the surface diffusivity of the catalyst and improve the activity and product selectivity of the catalyst; The support has an ammonia adsorption capacity of 0.25 to 0.65 mmol / g, preferably 0.3 to 0.6 mmol / g, more preferably 0.3 to 0.5 mmol / g; The content of alumina in the support is 65% by weight or more, preferably 70% by weight or more, more preferably 75% by weight or more, based on the total amount of the matrix; the doping element is present in an amount of 0.05 to 6 wt.%, preferably 0.05 to 5 wt.%, more preferably 0.05 to 4.5 wt.%, particularly preferably 0.07 to 4 wt.% (e.g., 0.08 to 4 wt.% or 0.1 to 3 wt.% (e.g., 0.1 wt.%, 0.5 wt.%, 1 wt.%, 1.5 wt.%, 2 wt.%, 2.5 wt.%, 3 wt.%, or a value between any two thereof)) relative to the total weight of the matrix; The carrier is 100 to 220 m 2 / g, preferably 105 to 210 m 2 / g, more preferably 110 to 210 m 2 / g, particularly preferably 120 to 210 m 2 / g specific surface area; The carrier has a pore volume of 0.4 to 1.1 ml / g, preferably 0.43 to 1.1 ml / g, more preferably 0.45 to 1.1 ml / g, and particularly preferably 0.45 to 1 ml / g; and The isoelectric point of the support is 3 to 6, preferably 3.5 to 5.5.
[0031] In a preferred embodiment of the catalyst of the present application, the active metal component is present in an amount of 5 to 45 g, preferably 8 to 44 g, more preferably 10 to 38 g, and particularly preferably 15 to 37 g per 100 g of the matrix.
[0032] In a preferred embodiment, the active metal component has a particle size of less than 10 nm, more preferably from 3 nm to 8 nm, which can be well matched to the properties of the support, thereby achieving better catalytic activity and product selectivity.
[0033] In a preferred embodiment, the catalyst further comprises a metal promoter supported on the support, the metal promoter comprising at least one metal selected from the group consisting of Group VIB, Group VIIB, Group IB, Group IIB and the Lanthanides, preferably at least one metal selected from the group consisting of Cr, Mo, W, Mn, Re, Cu, Ag, Au, Zn, La and Ce; more preferably the metal promoter is present in an amount of 0 to 10 g, preferably 0.1 to 10 g, more preferably 0.5 to 8 g per 100 g of the matrix.
[0034] In some further preferred embodiments, the metal promoter comprises a combination of at least one Group VIIB metal and at least one Group IB metal, wherein the weight ratio of the Group VIIB metal to the Group IB metal, calculated as elemental metals, is 0.05 to 15:1, preferably 0.1 to 12:1; or the metal promoter comprises a combination of at least one Group VIIB metal and at least one Group IIB metal, wherein the weight ratio of the Group VIIB metal to the Group IIB metal, calculated as elemental metals, is 0.2 to 20:1, preferably 0.3 to 6:1; or the metal promoter comprises a combination of at least one Group VIB metal, at least one Group IB metal and at least one Group IIB metal, wherein the weight ratio of the Group VIB metal to the Group IB metal to the Group IIB metal, calculated as elemental metals, is 0.1 to 10:0.1 to 10:1, preferably 0.2 to 8:0.2 to 8:1. Particularly preferably, the Group VIIB metal is selected from manganese and / or rhenium, the Group IB metal is at least one selected from the group consisting of copper, silver and gold, the Group IIB metal is selected from zinc, and the Group VIB metal is selected from molybdenum and / or tungsten.
[0035] In another preferred embodiment, the catalyst further comprises a metal promoter supported on the support, the metal promoter being a combination of at least one Group IIA metal, at least one Group IIB metal, and at least one Group VA metal. More preferably, the metal promoter is present in an amount of 0.1 to 10 g, preferably 0.5 to 6 g, per 100 g of the matrix. Even more preferably, the weight ratio of the Group IIA metal, the Group IIB metal, and the Group VA metal in the metal promoter is 0.1 to 10:0.1 to 10:1, preferably 0.2 to 8:0.2 to 8:1. Particularly preferably, the Group IIA metal is at least one selected from the group consisting of magnesium, calcium, and barium, the Group IIB metal is selected from zinc, and / or the Group VA metal is selected from bismuth.
[0036] According to the present application, the support for the catalyst can be obtained by any method known in the art that is useful for producing a support having the above-mentioned properties, although not particularly limited thereto. Preferably, the support can be prepared by a method comprising the following steps: successively molding, drying, and calcining a mixture containing a doping element and a matrix or a precursor thereof to obtain a support, wherein the matrix is selected from alumina, silica, molecular sieves, diatomaceous earth, aluminosilicates, or combinations thereof. The molecular sieve can be, for example, ZSM-5 molecular sieve or ZSM-11 molecular sieve. When a matrix precursor is used, the alumina precursor can be pseudoboehmite, and the silica precursor can be silicic acid, orthosilicic acid, or silica gel.
[0037] In the aforementioned method for producing a carrier, the matrix precursor is preferably pseudo-boehmite. Pseudo-boehmite can be prepared by at least one of the carbonization method, organoaluminum hydrolysis method, aluminum sulfate method, and nitric acid method. The specific surface area of pseudo-boehmite is preferably 250 to 400 m. 2 / g, preferably 255 to 360 m 2 / g, more preferably 255 to 340 m 2 / g, particularly preferably 260 to 330m 2 The pseudoboehmite preferably has a pore volume of 0.5 to 1.3 ml / g, more preferably 0.75 to 1.25 ml / g, more preferably 0.78 to 1.2 ml / g, and particularly preferably 0.78 to 1.1 ml / g. By using pseudoboehmite with a specific pore structure, a catalyst with better performance can be obtained.
[0038] In the above-mentioned method for producing a support, if the raw material providing the precursor of the matrix already contains the desired amount of doping element, molding can be simply carried out using such raw material, and if the raw material providing the precursor of the matrix does not contain the doping element or the content of the doping element is low (insufficient), additional doping element can be introduced.
[0039] In the aforementioned support manufacturing method, the doping element may be provided using a support modifier containing at least one compound capable of providing nonmetallic acid radical ions (e.g., inorganic acids and / or inorganic salts containing nonmetallic acid radicals), where the nonmetallic acid radical ions are preferably at least one selected from the group consisting of borate ions, fluoride ions, phosphate ions, sulfate ions, and selenate ions. More preferably, the support modifier is at least one selected from the group consisting of boric acid, nickel borate, cobalt borate, potassium borate, ammonium borate, magnesium borate, potassium fluoride, magnesium fluoride, cobalt fluoride, nickel fluoride, hydrofluoric acid, ammonium fluoride, phosphoric acid, aluminum phosphate, tripotassium phosphate, potassium dihydrogen phosphate, potassium hydrogen phosphate, magnesium phosphate, calcium phosphate, ammonium phosphate, sulfuric acid, cobalt sulfate, nickel sulfate, aluminum sulfate, calcium sulfate, potassium sulfate, magnesium sulfate, strontium phosphate, strontium sulfate, and selenic acid.
[0040] In the above-mentioned method for producing the carrier, the forming method may be selected from kneading, rolling, peeling, and the like.
[0041] In the aforementioned method for preparing the support, the support modifier is used in an amount such that the content of the doping element is 0.05 to 6 wt %, preferably 0.05 to 5 wt %, more preferably 0.05 to 4.5 wt %, and particularly preferably 0.07 to 4 wt % (e.g., 0.08 to 4 wt %), based on the total weight of the matrix. Those skilled in the art can determine the amount of the component raw materials (e.g., support modifier) based on the amount of said components in the final support; therefore, the amounts of some raw materials are not specified herein.
[0042] In the aforementioned method for producing a carrier, drying conditions may include a temperature of 80 to 150°C (e.g., 80°C, 85°C, 90°C, 95°C, 100°C, 110°C, 115°C, 120°C, 125°C, 130°C, 140°C, 150°C, or a value between any two of them), preferably 85 to 130°C, and a time of 6 to 20 hours (e.g., 6 hours, 7 hours, 7.5 hours, 8 hours, 8.5 hours, 9 hours, 10 hours, 12 hours, 15 hours, 18 hours, 20 hours, or a value between any two of them), preferably 10 to 20 hours.
[0043] In the aforementioned method for producing a carrier, the calcination conditions may include a temperature of 500 to 1120°C (e.g., 500 to 650°C, preferably 700 to 1100°C, more preferably 800 to 1050°C (e.g., 800°C, 850°C, 860°C, 870°C, 880°C, 890°C, 900°C, 920°C, 950°C, 960°C, 980°C, 1000°C, 1050°C, or a value between any two of them)) and a time of 2 to 20 hours (e.g., 2 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 6 hours, 7 hours, 8 hours, 10 hours, 15 hours, 20 hours, or any two of them).
[0044] The catalyst of the present application can be used after reduction. For example, it can be reduced using a hydrogen-containing gas at 350 to 500°C, preferably 350 to 450°C. The hydrogen-containing gas can be pure hydrogen or hydrogen diluted with an inert gas (e.g., a mixture of nitrogen and hydrogen). The reduction temperature is gradually increased during the reduction, and the temperature increase is preferably not too rapid (e.g., 20°C or less per hour). The reduction time can be determined by observing the production of HO in the reduction system. That is, when no new HO is produced in the reduction system, the reduction is terminated. Those skilled in the art can select the reduction time accordingly, but a detailed description thereof will be omitted herein for brevity (e.g., the reduction time can be 2 to 5 hours at the highest temperature). The reduction can be carried out directly in the reactor, followed by a catalytic reaction. The reduction can also be carried out in a separate reactor, also known as extra-reactor reduction. Before the catalyst is discharged from the reactor, it may be reduced with an oxygen-containing gas mixture and then passivated. The passivation temperature is, for example, 10 to 60°C, particularly 20 to 40°C. The catalyst that has undergone extra-reactor reduction and passivation can be activated, for example, at 150 to 250°C, preferably 170 to 200°C, before using hydrogen or a mixture of hydrogen and nitrogen. The activation time can be determined by observing the generation of HO in the activation system. That is, when no new HO is generated in the activation system, activation is terminated. Those skilled in the art can select the activation time accordingly, but a detailed description thereof will be omitted herein for brevity. For example, the activation time at the highest temperature may be, for example, 1 to 5 hours, preferably 2 to 3 hours. Alternatively, the catalyst can be used without activation, depending on the degree to which the active metal component and metal promoter of the catalyst have been oxidized.
[0045] In a second aspect, there is provided a method for producing the catalyst of the present application, comprising the following steps 1) to 3): 1) providing an inorganic porous support containing aluminum and / or silicon, wherein the support has an L acid content of 85% or more based on the total of the L acid content and the B acid content; 2) supporting the active metal component and optionally the metal promoter on the support; and 3) subjecting the material obtained in step 2) to a heat treatment and optionally a reduction treatment to obtain the catalyst. In a preferred embodiment, the L acid content of the support is 88% or more, more preferably 90% or more, particularly preferably 92% or more based on the total of the L acid content and the B acid content.
[0046] In a preferred embodiment, the step of "providing an inorganic porous support containing aluminum and / or silicon" in step 1) includes the step of continuously subjecting a mixture containing a doping element and a matrix or its precursor to shaping, drying and firing to obtain the support, wherein the matrix is selected from alumina, silica, molecular sieve, diatomaceous earth, aluminosilicate or a combination thereof, preferably the alumina precursor has a specific surface area of 250 - 400 m 2 / g, preferably 255 - 360 m 2 / g, more preferably 255 - 340 m 2 / g, particularly preferably 260 - 330 m 2 / g, and is pseudo-boehmite having a pore volume of 0.5 - 1.3 ml, preferably 0.75 - 1.25 ml / g, more preferably 0.78 - 1.2 ml / g, particularly preferably 0.78 - 1.1 ml / g; the doping element is a non-metal element, preferably at least one selected from the group consisting of group IIIA non-metal elements, group VA non-metal elements, group VIA non-metal elements and group VIIA non-metal elements excluding chlorine, preferably at least one selected from the group consisting of boron, fluorine, phosphorus, sulfur and selenium.
[0047] In a further preferred embodiment, the doping element is provided using a support modifier, which may be selected as described above in the first aspect, a detailed description of which is omitted herein for brevity. Even more preferably, the support modifier is used in an amount such that the resulting support has a doping element content of 0.05 to 6 wt. %, preferably 0.05 to 5 wt. %, more preferably 0.05 to 4.5 wt. %, and particularly preferably 0.07 to 4 wt. % (e.g., 0.08 to 4 wt. % or 0.1 to 3 wt. %, e.g., 0.1 wt. %, 0.5 wt. %, 1 wt. %, 1.5 wt. %, 2 wt. %, 2.5 wt. %, 3 wt. %, or a value between any two thereof) based on the total weight of the matrix.
[0048] In a further preferred embodiment, the shaping method may be selected from kneading, rolling, peeling, and the like.
[0049] In a further preferred embodiment, the drying conditions in step 1) include a temperature of 80 to 150°C and a drying time of 6 to 20 hours; and / or the firing conditions include a temperature of 500 to 1120°C, for example 500 to 650°C, preferably 700 to 1100°C, more preferably 800 to 1050°C, and a firing time of 2 to 20 hours.
[0050] In a further preferred embodiment, said step 1) has the features as described above for the method for producing said carrier in the first aspect, a detailed description of which will be omitted here for the sake of brevity.
[0051] In a preferred embodiment, the supporting step in step 2) comprises impregnating the support with a solution containing a precursor of the active metal component and, optionally, a precursor of the metal promoter, and the impregnation solution preferably has a pH in the range of 3.5 to 5.5. By controlling the pH of the impregnation solution within the aforementioned range, the dispersibility of the active metal component can be further improved.
[0052] According to the present application, impregnation is carried out by immersing the support in an appropriate solution containing precursors of the active metal component and the metal promoter, resulting in the precursors being supported on the support by adsorption. Impregnation methods can be classified into dry impregnation, wet impregnation, multiple impregnation, mixed impregnation, spray impregnation, etc. Dry impregnation and wet impregnation refer to impregnation of a support in a dry state or pre-wetted with water with precursors of the active metal component, respectively. Multiple impregnation refers to multiple impregnations with a mixed solution of precursors of one or more components, or multiple impregnations with various precursors, with drying and calcination required after each impregnation to "anchor" the impregnated components. Mixed impregnation refers to the joint impregnation of precursors of the active metal component and the metal promoter when no precipitation reaction occurs between the precursors of the active metal component. Spray impregnation refers to spraying an impregnation solution onto a continuously rotating support with a spray gun so that the impregnation solution just fills and saturates the pore volume of the support. These impregnation methods can be appropriately selected depending on the actual conditions for producing the catalyst of the present application.
[0053] In a preferred embodiment, the precursors of the active metal component and the metal promoter are soluble salts of the corresponding metals (e.g., nitrates, formates, oxalates, lactates, etc.). The solvent used to form the metal salt solution for impregnating the support is preferably water, although some organic solvents (e.g., ethanol, etc.) may also be used. The impregnation of the support with the metal salt solution can be carried out in any desired order or sequentially using multiple solutions containing one or more metal salts. All impregnation steps or a single impregnation step can be carried out in several stages, and the impregnation order can also be changed. The concentration of the solution is selected so that the desired amount of metal is supported on the support.
[0054] According to the present application, the support carrying the active metal component and, optionally, the metal promoter is subjected to heat treatment in step 3), which preferably includes calcination or a combination of drying and calcination. For example, the heat treatment may include a step of drying the impregnated support at 80 to 150°C, more preferably 80 to 120°C. The drying time can be appropriately selected depending on the drying temperature, the amount of material to be dried, the drying equipment, etc., and can be, for example, 6 to 20 hours, as long as the moisture content after drying does not affect the subsequent calcination. Furthermore, following drying, the support can be calcined at 150 to 500°C, preferably 300 to 500°C, for 1 to 6 hours to remove the water of crystallization in the salt or decompose the salt into an oxide. When performing multiple impregnations, it is preferable to perform drying and calcination after each impregnation.
[0055] In the present application, the process of supporting the active metal component and the metal promoter does not substantially affect the microstructure of the catalyst, and therefore the resulting catalyst has a pore structure similar to that of the support.
[0056] In a third aspect, the present application provides a support that is an inorganic porous material containing aluminum and / or silicon, wherein the support has an L acid content of 85% or more relative to the total of the L acid content and the B acid content.
[0057] In a preferred embodiment, the L acid content of the carrier is 88% or more, more preferably 90% or more, particularly preferably 92% or more, based on the total of the L acid content and the B acid content.
[0058] In a preferred embodiment, the support comprises a matrix and a doping element, the matrix being selected from alumina, silica, molecular sieve, diatomaceous earth, aluminosilicate, or a combination thereof, and the doping element is a non-metallic element, preferably at least one selected from the group consisting of Group IIIA non-metallic elements, Group VA non-metallic elements, Group VIA non-metallic elements, and Group VIIA non-metallic elements excluding chlorine, more preferably at least one selected from the group consisting of boron, fluorine, phosphorus, sulfur, and selenium.More preferably, the doping element in the support is derived from a non-metallic acid radical ion, and the non-metallic acid radical ion is preferably at least one selected from the group consisting of borate ions, fluoride ions, phosphate ions, sulfate ions, and selenate ions.
[0059] In a preferred embodiment, the carrier has at least one of the following characteristics: the ratio of the pore volume of pores having a pore diameter in the range of 7 to 27 nm to the pore volume of the support is more than 65%, preferably 70 to 90%, and the ratio of the pore volume of pores having a pore diameter of less than 7 nm to the pore volume of the support is 0 to 10%, preferably 0 to 8%; the ratio of the pore volume of pores having a pore diameter of less than 7.5 nm to the pore volume of the support is less than 20%, preferably 5 to 17%, the ratio of the pore volume of pores having a pore diameter of less than 9 nm to the pore volume of the support is less than 40%, the ratio of the pore volume of pores having a pore diameter of more than 27 nm to the pore volume of the support is less than 5%, preferably 0.5 to 5%, preferably the ratio of the pore volume of pores having a pore diameter of 7.5 nm or more and less than 9 nm to the pore volume of the support is 5 to 17%, and the ratio of the pore volume of pores having a pore diameter of 9 nm or more and 27 nm or less to the pore volume of the support is 61 to 89.5%; The support has an ammonia adsorption capacity of 0.25 to 0.65 mmol / g, preferably 0.3 to 0.6 mmol / g, more preferably 0.3 to 0.5 mmol / g; The content of alumina in the support is 65% by weight or more, preferably 70% by weight or more, more preferably 75% by weight or more, based on the total amount of the matrix; The content of the doping element is 0.05 to 6 wt %, preferably 0.05 to 5 wt %, more preferably 0.05 to 4.5 wt %, particularly preferably 0.07 to 4 wt %, based on the total amount of the matrix; The carrier is 100 to 220 m 2 / g, preferably 105 to 210 m 2 / g, more preferably 110 to 210 m 2 / g, particularly preferably 120 to 210 m 2 / g specific surface area; The carrier has a pore volume of 0.4 to 1.1 ml / g, preferably 0.43 to 1.1 ml / g, more preferably 0.45 to 1.1 ml / g, and particularly preferably 0.45 to 1 ml / g; and The isoelectric point of the support is 3 to 6, preferably 3.5 to 5.5.
[0060] In a fourth aspect, the present application provides the use of the catalyst according to the present application or the support according to the present application for producing an organic amine by catalytic amination.
[0061] In a fifth aspect, the present application provides a process for producing an organic amine, comprising the step of contacting an amination feedstock and an aminating agent with the catalyst according to the present application in the presence of hydrogen for an amination reaction to obtain an organic amine.
[0062] In a preferred embodiment, the amination raw material is selected from the group consisting of alcohols, ketones, alcoholamines, aldehydes, or combinations thereof, and is preferably selected from the group consisting of C2-C20 alcohols, C3-C20 ketones, C2-C20 alcoholamines, C2-C20 aldehydes, and mixtures thereof. More preferably, the amination raw material is ethanol, acetaldehyde, n-propanol, propionaldehyde, isopropanol, n-butanol, butyraldehyde, isobutanol, isobutyraldehyde, 2-ethylhexanol, 2-ethylhexaldehyde, octanol, octanal, dodecanol, dodecanal, hexadecanol, hexadecanal, cyclopentanol, cyclohexanol, cyclooctanol, cyclododecanol, benzyl alcohol, benzaldehyde, phenethyl alcohol, phenylacetaldehyde, 1,4- butanediol, 1,4-butanedial, 1,5-pentanediol, 1,5-glutaraldehyde, 1,6-hexanediol, 1,6-hexanedial, 1,8-octanediol, 1,8-octanedial, 1,12-dodecanediol, 1,12-dodecanedialdehyde, ethanolamine, propanolamine, isopropanolamine, 6-aminohexanol, diethanolamine, diisopropanolamine, dimethylethanolamine, acetone, ethylene glycol, 1,3-propanediol, and mixtures thereof.
[0063] In this application, the aminating agent refers to a reactant capable of providing an amino group and / or an amine group. Preferably, the aminating agent is selected from the group consisting of ammonia, primary amines, secondary amines, and combinations thereof, and more preferably, ammonia, C1-C12 primary amines, C2-C12 secondary amines, and mixtures thereof (e.g., at least one of alkylamines, cycloalkylamines, and aralkylamines, more preferably C1-C4 alkylamines). More preferably, the aminating agent is selected from the group consisting of ammonia, monomethylamine, dimethylamine, methylethylamine, monoethylamine, diethylamine, and mixtures thereof.
[0064] In a preferred embodiment, the amination conditions are as follows: a molar ratio of hydrogen to the aminating agent to the amination raw material is 1 to 6:2 to 35:1, preferably 1 to 6:2 to 33:1, and more preferably 1 to 5:3 to 33:1; a temperature is 105 to 230°C, preferably 110 to 220°C, and more preferably 110 to 210°C; a pressure is 0.7 to 25 MPa, preferably 1 to 25 MPa, more preferably 1 to 22 MPa, and particularly preferably 1 to 17 MPa; and a liquid phase volumetric space velocity of the amination raw material is 0.06 to 1 m 3 / (m 3 h) is included.
[0065] In some preferred embodiments, the amination raw material is a monohydric alcohol, and the amination conditions are such that the molar ratio of hydrogen to the aminating agent to the amination raw material is preferably 1 to 4:2 to 9:1, more preferably 1 to 4:2 to 8:1; the temperature is 130 to 210°C, preferably 130 to 208°C, more preferably 130 to 200°C; the pressure is 0.8 to 3.5 MPa, preferably 1 to 2.5 MPa; and the liquid phase volumetric space velocity of the amination raw material is 0.1 to 0.8 m 3 / (m 3 h) is included.
[0066] In some preferred embodiments, the amination raw material is a ketone or an aldehyde, and the amination conditions include a molar ratio of hydrogen to the aminating agent to the amination raw material of 1 to 4:2 to 6:1, and preferably 1 to 4:2 to 5:1; a temperature of 105 to 180°C, preferably 110 to 170°C, and more preferably 110 to 160°C; a pressure of 0.7 to 2.5 MPa, preferably 1 to 2.5 MPa, and more preferably 1 to 2 MPa; and a liquid phase volumetric space velocity of the amination raw material of 0.1 to 1 m 3 / (m 3 h), preferably 0.1 to 0.8 m 3 / (m 3 h).
[0067] In some preferred embodiments, the amination raw material is an alcohol amine, and the amination conditions are such that the molar ratio of hydrogen to the aminating agent to the amination raw material is 1 to 4:3 to 23:1, preferably 1 to 4:3 to 20:1, and more preferably 1 to 4:3 to 10:1; the temperature is 130 to 200°C; the pressure is 1 to 16 MPa, preferably 1 to 13 MPa, and more preferably 1 to 11 MPa; and the liquid phase volumetric space velocity of the amination raw material is 0.06 to 0.8 m 3 / (m 3 h) is included.
[0068] In some preferred embodiments, the amination raw material is a dihydric alcohol, and the amination conditions are such that the molar ratio of hydrogen to the aminating agent to the amination raw material is 0.3 to 5:2 to 35:1, preferably 1 to 4:3 to 35:1, more preferably 1 to 4:3 to 33:1, and particularly preferably 1 to 4:3 to 32:1; the temperature is 130 to 230°C, preferably 130 to 220°C, and more preferably 130 to 210°C; the pressure is 1 to 25 MPa, preferably 1 to 22 MPa, and more preferably 1 to 17 MPa; and the liquid phase volumetric space velocity of the amination raw material is 0.1 to 0.9 m 3 / (m 3 ·h), preferably 0.1 to 0.8 m 3 / (m 3 h) is included.
[0069] In some preferred embodiments, the amination feedstock is a mixture of 1,6-hexanediol, cycloheximide, and 6-amino-1-hexanol, and the amination conditions are a molar ratio of hydrogen to the aminating agent to the amination feedstock of 0.3 to 4:3 to 35:1, preferably 1 to 4:3 to 33:1, and more preferably 1 to 4:3 to 32:1; a temperature of 130 to 230°C, preferably 130 to 220°C, and more preferably 130 to 210°C; a pressure of 1 to 22 MPa, and preferably 1 to 17 MPa; and a liquid phase volumetric hourly space velocity of the amination feedstock of 0.1 to 0.9 m 3 / (m 3 ·h), preferably 0.1 to 0.8 m 3 / (m 3 h) is included.
[0070] First Type of Embodiment In a first type of embodiment of the present application, there is provided a catalyst having a function of catalyzing the hydroamination of an alcohol to produce an organic amine, the catalyst comprising a support, an active metal component supported on the support, and optionally a metal co-catalyst supported on the support, the support comprising a matrix and a doping element, the matrix comprising alumina and optionally an additional support, the additional support being at least one selected from the group consisting of silica, molecular sieves, and diatomaceous earth; and a pore volume of 7.5n of the active metal component supported on the support. The ratio of the pore volume of pores having a pore diameter of less than 9 nm to the pore volume of the support is less than 20%, the ratio of the pore volume of pores having a pore diameter of less than 9 nm to the pore volume of the support is less than 40%, and the ratio of the pore volume of pores having a pore diameter of more than 27 nm to the pore volume of the support is less than 5%; the support has an ammonia adsorption capacity of 0.3 to 0.6 mmol / g; the support has an L acid content of 90% or more relative to the total of the L acid content and the B acid content; and the active metal component is cobalt and / or nickel.
[0071] The catalyst of the first type of embodiment of the present application has a specific acidity and pore structure, and when used for alcohol hydroamination, the catalyst not only exhibits high catalytic activity but also excellent selectivity. When used for the hydroamination of 1,3-propanediol, the catalyst produces less 3-aminopropanol and other impurities; when used for the hydroamination of ethanol, the catalyst produces less methylethylamine, methyldiethylamine, ethyl-n-propylamine, and ethyl-sec-butylamine; and when used for the hydroamination of 1,6-hexanediol, the catalyst produces less heavy components and other impurities. After long-term service life evaluation, it was found that the catalyst of the first type of embodiment of the present application has stable catalytic performance, and by controlling the acidity of the catalyst within an appropriate range, the adsorption-desorption performance of the catalyst is also improved, further promoting the diffusion of the reaction system, accelerating the reaction rate, reducing carbon deposition, and delaying the blockage of the pore channels.
[0072] According to a first type of embodiment of the present application, the support is mainly composed of (doped) alumina and may further contain (doped) silica, etc., thereby further improving the properties of the catalyst (e.g., the type of pore channel structure and the stability of the pore structure, etc.). Preferably, the matrix in the support is selected from alumina doped with at least one of silica, molecular sieve, and diatomaceous earth, and undoped alumina, and the content of the alumina support in the matrix is 65% by weight or more, preferably 75% by weight or more, based on the total amount of the alumina support and the additional support.
[0073] Preferably, the doping element is present in the support in an amount of 0.05 to 3% by weight, more preferably 0.08 to 2% by weight, even more preferably 0.1 to 1.5% by weight, relative to the total weight of the matrix.
[0074] Preferably, the doping element in the support is derived from an acid radical ion, excluding chloride ion. The doping element is introduced during the preparation of the support, so that the doping element is mainly present in the bulk phase of the support. The acid radical ion may be at least one selected from non-metal acid radical ions, more preferably at least one selected from the group consisting of borate ions, fluoride ions, phosphate ions, sulfate ions, and selenate ions. The doping element is preferably at least one selected from the group consisting of boron, fluorine, phosphorus, sulfur, and selenium.
[0075] Preferably, the ratio of the pore volume of pores having a pore diameter of less than 7.5 nm to the pore volume of the support is 5 to 17%, more preferably 5 to 10%, the ratio of the pore volume of pores having a pore diameter of 7.5 nm or more but less than 9 nm to the pore volume of the support is 5 to 17%, the ratio of the pore volume of pores having a pore diameter of 9 nm or more but less than 27 nm to the pore volume of the support is 61 to 89.5%, and the ratio of the pore volume of pores having a pore diameter of more than 27 nm to the pore volume of the support is 0.5 to 5%, more preferably 0.5 to 3%. The present inventors have found that a catalyst having a pore channel structure that satisfies the above requirements has better catalytic performance.
[0076] Preferably, the carrier has an ammonia adsorption capacity of 0.3 to 0.5 mmol / g.
[0077] Preferably, the carrier has an L acid content of 92 to 100%, preferably 96 to 100%, based on the sum of the L acid content and the B acid content.
[0078] Preferably, the carrier has a thickness of 105 to 220 m 2 / g specific surface area.
[0079] Preferably, the support has a pore volume of 0.4 to 1.1 ml / g.
[0080] According to a first type of embodiment of the present application, the active metal component may be present in an amount of 5 to 42 g, preferably 10 to 35 g, per 100 g of the matrix.
[0081] According to a first type of embodiment of the present application, in order to better demonstrate the performance of the catalyst, optimize the ratio of reaction products, and reduce undesired side reactions, the catalyst may further contain a metal promoter, which may be at least one selected from the group consisting of Group VIB, Group VIIB, Group IB, Group IIB, and Lanthanide elements, and preferably at least one of Cr, Mo, W, Mn, Re, Cu, Ag, Au, Zn, La, and Ce. Preferably, the metal promoter is present in an amount of 0 to 10 g, preferably 0.5 to 6 g, per 100 g of the matrix.
[0082] In a first type of embodiment of the present application, there is also provided a process for producing an organic amine, comprising the step of contacting an amination feedstock and an aminating agent with the catalyst as described above in the presence of hydrogen for an amination reaction.
[0083] According to a first type of embodiment of the present application, the aminating raw material or aminating agent can be selected as described above, and a detailed description thereof will be omitted herein for the sake of brevity.
[0084] According to a first type embodiment of the present application, the amination conditions are such that the molar ratio of hydrogen to the aminating agent to the aminating raw material is 1 to 5:2 to 35:1, the temperature is 110 to 220°C, the pressure is 1 to 25 MPa, and the liquid phase volumetric space velocity of the aminating raw material is 0.06 to 1 m 3 / (m 3 h).
[0085] Preferably, the amination raw material is a monohydric alcohol, and the amination conditions are a molar ratio of hydrogen to the aminating agent to the amination raw material of 1 to 4:2 to 8:1, a temperature of 130 to 200°C, a pressure of 1 to 3.5 MPa, and a liquid phase volumetric space velocity of the amination raw material of 0.1 to 0.8 m 3 / (m 3 h) is included.
[0086] Preferably, the amination raw material is a ketone or an aldehyde, and the amination conditions are a molar ratio of hydrogen to the aminating agent to the amination raw material of 1 to 4:2 to 5:1, a temperature of 110 to 180°C, a pressure of 1 to 2.5 MPa, and a liquid phase volumetric space velocity of the amination raw material of 0.1 to 0.8 m 3 / (m 3 h) is included.
[0087] Preferably, the amination raw material is an alcohol amine, and the amination conditions are a molar ratio of hydrogen to the aminating agent to the amination raw material of 1 to 4:3 to 20:1, a temperature of 130 to 200°C, a pressure of 1 to 11 MPa, and a liquid phase volumetric space velocity of the amination raw material of 0.06 to 0.8 m 3 / (m 3 h) is included.
[0088] Preferably, the amination raw material is a dihydric alcohol, and the amination conditions are a molar ratio of hydrogen to the aminating agent to the amination raw material of 1 to 5:2 to 35:1, a temperature of 130 to 220°C, a pressure of 1 to 25 MPa, and a liquid phase volumetric space velocity of the amination raw material of 0.1 to 0.8 m 3 / (m 3 h) is included.
[0089] Preferably, the amination raw material is a mixture of 1,6-hexanediol, hexamethyleneimine, and 6-amino-1-hexanol (abbreviated as aminohexanol), and the amination conditions are a molar ratio of hydrogen to the aminating agent to the amination raw material of 1 to 4:3 to 35:1, a temperature of 130 to 200°C, a pressure of 1 to 22 MPa, and a liquid phase volumetric space velocity of the amination raw material of 0.1 to 0.8 m 3 / (m 3 h) is included.
[0090] Second Type of Embodiment In a second type of embodiment of the present application, there is provided a catalyst having a function of catalyzing the production of amines from alcohols, the catalyst comprising a support, an active metal component supported on the support, and optionally a metal co-catalyst supported on the support, wherein the support is at least one selected from the group consisting of doped alumina, doped silica, doped molecular sieve, and doped diatomaceous earth; the support has an ammonia adsorption capacity of 0.25 to 0.65 mmol / g; the support has an L acid content of 88% or more relative to the total of the L acid content and the B acid content; the active metal component is cobalt and / or nickel, and the particle size of the active metal component in the catalyst is less than 10 nm.
[0091] The catalyst of the second type of embodiment of the present application has improved support acidity, highly dispersed active metal components, and a particle size of less than 10 nm, exhibiting higher catalytic activity and, at the same time, higher selectivity when used for the hydroamination of alcohols. When the catalyst is used for the hydroamination of ethanolamine, it produces less components other than ethylenediamine (e.g., piperazine); and when the catalyst is used for the hydroamination of 1,6-hexanediol, it produces less heavy components and other impurities. After a long-term evaluation period, the catalyst of the second type of embodiment of the present application exhibited stable catalytic performance. It was found that controlling the acidity of the catalyst within an appropriate range improved the adsorption-desorption performance of the catalyst, thereby promoting the diffusion of the reaction system, accelerating the reaction rate, reducing carbon deposition, and delaying the blockage of pore channels.
[0092] According to a second type of embodiment of the present application, the support comprises a matrix selected from the group consisting of alumina, silica, molecular sieve, diatomaceous earth, etc., and a doping element. Preferably, the doping element is present in the support in an amount of 0.05 to 5 wt %, more preferably 0.08 to 4 wt %, relative to the total weight of the matrix.
[0093] Preferably, the doping element in the support is derived from an acid radical ion, excluding chloride ions. The doping element is preferably at least one selected from the group consisting of boron, fluorine, phosphorus, sulfur, and selenium. The doping element is introduced during the preparation of the support, so that the doping element is present in the bulk phase of the support. More preferably, the acid radical ion may be at least one selected from the group consisting of non-metal acid radical ions (e.g., at least one selected from the group consisting of borate ions, fluoride ions, phosphate ions, sulfate ions, and selenate ions).
[0094] Preferably, the support has an ammonia adsorption capacity of 0.3 to 0.5 mmol / g (e.g., 0.3 mmol / g, 0.32 mmol / g, 0.35 mmol / g, 0.38 mmol / g, 0.4 mmol / g, 0.45 mmol / g, 0.48 mmol / g, 0.5 mmol / g, or a value between any two thereof).
[0095] Preferably, the carrier has an L acid content of 90 to 100% of the total of the L acid content and the B acid content.
[0096] Preferably, the active metal component of the catalyst has a particle size of from 3 nm to 8 nm.
[0097] Preferably, the carrier has a diameter of 100 to 200 m 2 / g specific surface area.
[0098] Preferably, the support has a pore volume of 0.45 to 1 ml / g.
[0099] Preferably, the carrier has an isoelectric point of 3 to 6, preferably 3.5 to 5.5.
[0100] Preferably, the content of the active metal component in the support may be 7 to 45 g, preferably 12 to 38 g, per 100 g of the matrix.
[0101] According to a second type of embodiment of the present application, the catalyst may further contain a metal promoter to improve the catalytic performance, optimize the ratio of reaction products, and reduce undesired side reactions. The metal promoter may be at least one selected from the group consisting of Group VIB elements, Group VIIB elements, Group IB elements, Group IIB elements, and Lanthanide elements, and preferably at least one of Cr, Mo, W, Mn, Re, Cu, Ag, Au, Zn, La, and Ce. Preferably, the metal promoter is present in the support in an amount of 0 to 10 g, preferably 0.5 to 6 g, per 100 g of the matrix. More preferably, the particle size of the metal promoter is less than 10 nm.
[0102] In a second type of embodiment of the present application, there is also provided a process for producing an organic amine, comprising the step of contacting an amination feedstock and an aminating agent with the catalyst as described above in the presence of hydrogen for an amination reaction.
[0103] According to a second type of embodiment of the present application, the aminating raw material or aminating agent can be selected as described above, and a detailed description thereof will be omitted herein for the sake of brevity.
[0104] According to a second type of embodiment of the present application, the amination conditions are such that the molar ratio of hydrogen to the aminating agent to the aminating raw material is 1 to 5:3 to 33:1, the temperature is 110 to 210°C, the pressure is 1 to 22 MPa, and the liquid phase volumetric space velocity of the aminating raw material is 0.06 to 1 m 3 / (m 3 h).
[0105] Preferably, the amination raw material is a monohydric alcohol, and the amination conditions are a molar ratio of hydrogen to the aminating agent to the amination raw material of 1 to 4:2 to 8:1, a temperature of 130 to 200°C, a pressure of 0.8 to 2.5 MPa, and a liquid phase volumetric space velocity of the amination raw material of 0.1 to 0.8 m 3 / (m3 h) is included.
[0106] Preferably, the amination raw material is a ketone or an aldehyde, and the amination conditions are a molar ratio of hydrogen to the aminating agent to the amination raw material of 1 to 4:2 to 6:1, a temperature of 110 to 170°C, a pressure of 1 to 2.5 MPa, and a liquid phase volumetric space velocity of the amination raw material of 0.1 to 0.8 m 3 / (m 3 h) is included.
[0107] Preferably, the amination raw material is an alcohol amine, and the amination conditions are a molar ratio of hydrogen to the aminating agent to the amination raw material of 1 to 4:3 to 10:1, a temperature of 130 to 200°C, a pressure of 1 to 11 MPa, and a liquid phase volumetric space velocity of the amination raw material of 0.06 to 0.8 m 3 / (m 3 h) is included.
[0108] Preferably, the amination raw material is a mixture of 1,6-hexanediol, hexamethyleneimine, and 6-amino-1-hexanol (abbreviated as aminohexanol) or a dihydric alcohol, and the amination conditions are a molar ratio of hydrogen to the aminating agent to the amination raw material of 1 to 4:3 to 33:1, a temperature of 130 to 210°C, a pressure of 1 to 22 MPa, and a liquid phase volumetric space velocity of the amination raw material of 0.1 to 0.8 m 3 / (m 3 h) is included.
[0109] Third Type of Embodiment In a third type of embodiment of the present application, there is provided a catalyst having a function of producing an amine by the hydroamination of an alcohol, the catalyst comprising a support, an active metal component supported on the support, and optionally a metal promoter supported on the support, the support comprising a matrix and a doping element, the matrix comprising alumina, and optionally an additional support selected from silica and / or molecular sieves, the doping element being at least one selected from the group consisting of boron, fluorine, phosphorus, sulfur, and selenium; the ratio of the pore volume of pores having a pore diameter in the range of 7 to 27 nm to the pore volume of the support is greater than 65%; the support has an L acid content of 85% or more relative to the total of the L acid content and the B acid content; and the active metal component is cobalt and / or nickel.
[0110] By doping the support with boron, fluorine, phosphorus, sulfur, and selenium, the catalyst according to the third type of embodiment of the present application exhibits improved catalytic performance (e.g., for the hydroamination of ethanol), with less production of methylethylamine, methyldiethylamine, ethyl-n-propylamine, and ethyl-sec-butylamine. When the catalyst is used for the hydroamination of 1,6-hexanediol, less heavy components and other impurities are produced, and the catalyst's service life is longer.
[0111] Furthermore, when the catalyst of the third type embodiment of the present application has a specific pore channel structure and is used for the hydroamination of alcohols, the catalyst exhibits high catalytic activity and has excellent selectivity and stability, thereby reducing carbon deposition in the pore channels and effectively preventing blockage of the pore channels of the catalyst.
[0112] According to a third type of embodiment of the present application, the support is mainly composed of doped alumina and may further contain (doped) silica, etc., thereby further improving the pore channel structure and acid-base properties of the support of the catalyst. Preferably, the matrix in the support is alumina doped with silica and / or molecular sieve, and the content of the alumina support in the matrix is 70 wt % or more, preferably 75-100 wt %.
[0113] Preferably, the doping element is present in the support in an amount of 0.05 to 6% by weight, more preferably 0.08 to 4% by weight, relative to the total weight of the matrix.
[0114] Preferably, the doping element is incorporated into the support in the form of at least one selected from the group consisting of borate ions, fluoride ions, phosphate ions, sulfate ions and selenate ions, and is introduced during the preparation of the support so that the doping element is mainly present in the bulk phase of the support.
[0115] Preferably, the ratio of the pore volume of pores having a pore diameter in the range of 7 to 27 nm to the pore volume of the support is greater than 65%. More preferably, the ratio of the pore volume of pores having a pore diameter in the range of 7 to 27 nm to the pore volume of the support is 70 to 90%. Even more preferably, the ratio of the pore volume of pores having a pore diameter less than 7 nm to the pore volume of the support is 0 to 10%, and the ratio of the pore volume of pores having a pore diameter greater than 27 nm to the pore volume of the support is 18 to 32%.
[0116] Preferably, the carrier has an L acid content of 85 to 98% based on the total of the L acid content and the B acid content.
[0117] Preferably, the carrier has a thickness of 120 to 210 m 2 / g specific surface area.
[0118] Preferably, the support has a pore volume of 0.43 to 1.1 ml / g.
[0119] Preferably, the active metal component may be present in an amount of 8 to 44 g, preferably 12 to 37 g, per 100 g of the matrix.
[0120] Preferably, the metal promoter may be present in an amount of 0 to 10 g, preferably 0.5 to 6 g, per 100 g of the matrix.
[0121] According to a third type of embodiment of the present application, the catalyst may further comprise a metal promoter to better demonstrate the performance of the catalyst, optimize the ratio of reaction products, and reduce undesired side reactions. The metal promoter may be at least one selected from the group consisting of Group VIB, Group VIIB, Group IB, Group IIB, and the lanthanide series elements, and preferably at least one of Cr, Mo, W, Mn, Re, Cu, Ag, Au, Zn, La, and Ce.
[0122] In a third type of embodiment of the present application, there is also provided a process for producing an organic amine, comprising the step of contacting an amination feedstock and an aminating agent with the catalyst as described above in the presence of hydrogen for an amination reaction.
[0123] According to a third type of embodiment of the present application, the amination raw material and aminating agent can be selected as described above, and detailed descriptions thereof will be omitted herein for the sake of brevity.
[0124] According to a third type embodiment of the present application, the amination conditions are such that the molar ratio of hydrogen to the aminating agent to the aminating raw material is 1 to 6:2 to 32:1, the temperature is 105 to 210°C, the pressure is 1 to 17 MPa, and the liquid phase volumetric space velocity of the aminating raw material is 0.06 to 1 m 3 / (m 3 h).
[0125] Preferably, the amination raw material is a monohydric alcohol, and the amination conditions are a molar ratio of hydrogen to the aminating agent to the amination raw material of 1 to 4:2 to 9:1, a temperature of 130 to 208°C, a pressure of 1 to 2.5 MPa, and a liquid phase volumetric space velocity of the amination raw material of 0.1 to 0.8 m 3 / (m 3 h) is included.
[0126] Preferably, the amination raw material is a ketone or an aldehyde, and the amination conditions are such that the molar ratio of hydrogen to the aminating agent to the amination raw material is 1 to 4:2 to 5:1, the temperature is 105 to 160°C, the pressure is 1 to 2 MPa, and the liquid phase volumetric space velocity of the amination raw material is 0.1 to 1 m 3 / (m 3 h) is included.
[0127] Preferably, the amination raw material is an alcohol amine, and the amination conditions are a molar ratio of hydrogen to the aminating agent to the amination raw material of 1 to 4:3 to 20:1, a temperature of 130 to 200°C, a pressure of 1 to 13 MPa, and a liquid phase volumetric space velocity of the amination raw material of 0.06 to 0.8 m 3 / (m 3 h) is included.
[0128] Preferably, the amination raw material is a mixture of 1,6-hexanediol, hexamethyleneimine, and 6-amino-1-hexanol (abbreviated as aminohexanol) or a dihydric alcohol, and the amination conditions are a molar ratio of hydrogen to the aminating agent to the amination raw material of 1 to 4:3 to 32:1, a temperature of 130 to 210°C, a pressure of 1 to 17 MPa, and a liquid phase volumetric space velocity of the amination raw material of 0.1 to 0.9 m 3 / (m 3 h) is included.
[0129] Fourth Type of Embodiment In a fourth type of embodiment of the present application, there is provided a catalyst having the function of catalyzing the production of amines from alcohols, the catalyst comprising a support, an active metal component supported on the support, and a metal promoter supported on the support, wherein the support has an L acid content of 85% or more based on the sum of the L acid content and the B acid content, the active metal component being cobalt and / or nickel; and the metal promoter being a combination of at least one Group IIA metal, at least one Group IIB metal, and at least one Group VA metal.
[0130] The catalyst of the fourth type of embodiment of the present application contains a specific metal promoter and has high catalytic activity, and at the same time has high selectivity and produces almost no by-products.
[0131] Preferably, the carrier has an L acid content of 88% or more, more preferably 90% or more, particularly preferably 92% or more, based on the sum of the L acid content and the B acid content.
[0132] Preferably, the support comprises a matrix and a doping element, the matrix comprising alumina and, optionally, an additional support comprising silica and / or a molecular sieve; the doping element is at least one selected from the group consisting of boron, fluorine, phosphorus, sulfur, and selenium; and the ratio of the pore volume of pores having a pore diameter in the range of 7 to 27 nm to the pore volume of the support is greater than 65%.
[0133] According to a fourth embodiment of the present application, the support is mainly composed of doped alumina and may further contain (doped) silica, etc., thereby further improving the pore channel structure of the catalyst, thereby allowing easy diffusion of reactants and products in the pore channels and providing a more stable pore structure. Preferably, the alumina content of the matrix in the support is 70% by weight or more, preferably 75-100% by weight, based on the total amount of alumina and the additional support.
[0134] Preferably, the doping element is present in the support in an amount of 0.05 to 4.5% by weight, more preferably 0.07 to 2.8% by weight, relative to the total weight of the matrix.
[0135] Preferably, the doping element is incorporated into the support in the form of at least one selected from the group consisting of borate ions, fluoride ions, phosphate ions, sulfate ions, and selenate ions. The doping element is present in the alumina precursor. If the doping element is introduced during the preparation of the precursor, the doping element is enclosed in the crystalline phase of the precursor. If the doping element is introduced after the preparation of the support, the doping element is mainly present in the bulk phase of the support.
[0136] Preferably, the ratio of the pore volume of pores having a pore diameter in the range of 7 to 27 nm to the total pore volume of the support is 70 to 90%. Preferably, the ratio of the pore volume of pores having a pore diameter of less than 7 nm to the total pore volume of the support is 0 to 8%. Preferably, the ratio of the pore volume of pores having a pore diameter of more than 27 nm to the total pore volume of the support is 15 to 35%, more preferably 20 to 29%.
[0137] Preferably, the carrier has a thickness of 110 to 210 m 2 / g specific surface area.
[0138] Preferably, the support has a pore volume of 0.45 to 1.1 ml / g.
[0139] Preferably, the active metal component is present in an amount of 8 to 45 g, preferably 15 to 38 g (e.g., 15, 20, 25, 28, 30, 32, 35, 37, 38, or a value between any two thereof) per 100 g of the matrix.
[0140] Preferably, the metal promoter is present in an amount of 0.1 to 10 g, preferably 0.5 to 6 g (e.g., 0.5, 1, 2, 3, 3.5, 3.8, 4, 4.2, 4.5, 4.8, 5, 5.2, 5.5, 6, or a value between any two thereof) per 100 g of the matrix.
[0141] According to a fourth type of embodiment of the present application, the catalyst may contain a metal promoter as described above to better demonstrate the performance of the catalyst, optimize the ratio of reaction products, and reduce undesirable side reactions. The weight ratio of the Group IIA metal, the Group IIB metal, and the Group VA metal in the metal promoter is preferably 0.1-10:0.1-10:1, more preferably 0.2-8:0.2-8:1. Preferably, the Group IIA metal is at least one selected from the group consisting of magnesium, calcium, and barium. Preferably, the Group IIB metal is selected from zinc. Preferably, the Group VA metal is selected from bismuth.
[0142] In a fourth embodiment of the present application, the use of a support with a specific pore structure and doping elements allows the catalyst to exhibit high catalytic activity and, at the same time, higher selectivity when used for the hydroamination of alcohols. When the catalyst is used for the hydroamination of ethanol, the production of methylethylamine, methyldiethylamine, ethyl-n-propylamine, and ethyl-sec-butylamine is reduced. When the catalyst is used for the hydroamination of 1,6-hexanediol, the production of heavy components and other impurities is reduced. After long-term testing, it was found that the catalyst has stable catalytic performance, promotes the diffusion of reaction systems, accelerates the reaction rate, reduces carbon deposition, and delays the blockage of pore channels.
[0143] According to a fourth type of embodiment of the present application, the support can be prepared using a known method that can provide the doping element, the pore structure that satisfies the above-mentioned range, etc., and obtaining the support having the doping element and the pore structure that satisfies the above-mentioned range can be achieved by a person skilled in the art. Preferably, the support is prepared by a method including the following steps (1) and (2): (1) sequentially shaping, first drying and first calcining a mixture comprising a doping element, an alumina precursor and optionally an additional support precursor, wherein the additional support precursor comprises a silica precursor (e.g., silica sol) and / or a molecular sieve precursor (e.g., ZSM-5); (2) mixing the product of the first calcination with a solution of a Group IIA metal precursor, followed by a second drying and a second calcination. The shaping method may include kneading, rolling, or peeling.
[0144] In the above-mentioned method for producing a support, if the raw material providing the precursor of the support already contains a desired amount of a doping element, molding can be easily carried out using such raw material, and if the raw material providing the precursor of the support does not contain a doping element or has a low (insufficient) content of the doping element, it can be understood by those skilled in the art that additional doping elements can be introduced.
[0145] In the aforementioned methods for preparing the support, the doping element may be incorporated into the raw material providing the alumina precursor, or the alumina precursor and / or additional support precursor modified with the doping element may be used directly, and such alumina precursor or additional support precursor modified with the doping element may be obtained commercially or by conventional methods, the detailed description of which is omitted herein for the sake of brevity.
[0146] In the above-mentioned methods for preparing the support, a person skilled in the art can determine the amount of raw materials (e.g., support modifiers) for a component (e.g., a doping element) based on the amount of said component in the final support, and therefore the amount of some raw materials is not given herein.
[0147] In the above-mentioned method for producing a carrier, the alumina precursor is preferably pseudo-boehmite. The specific surface area of the pseudo-boehmite is preferably 250 to 330 m 2 / g. The pore volume of the pseudo-boehmite is preferably 0.5 to 1.1. Pseudo-boehmite can be produced by at least one of the carbonization method, organoaluminum hydrolysis method, aluminum sulfate method, and nitric acid method, and is particularly preferably produced by the aluminum sulfate method. By using pseudo-boehmite with a specific pore structure, a catalyst with better performance can be obtained.
[0148] In the aforementioned method for producing a carrier, the first drying conditions and the second drying conditions may each independently include a temperature of 80 to 150°C and a drying time of 6 to 20 hours, preferably a temperature of 100 to 120°C and a drying time of 8 to 15 hours.
[0149] In the above-described method for producing a support, the conditions for the first calcination may include a temperature of 500 to 650° C. and a calcination time of 2 to 20 hours, preferably a temperature of 520 to 620° C. and a calcination time of 4 to 8 hours.
[0150] In the above-described method for producing a support, the conditions for the second calcination may include a temperature of 800 to 1100°C and a calcination time of 2 to 20 hours, preferably 800 to 980°C and a calcination time of 5 to 10 hours.
[0151] In a fourth type of embodiment of the present application, there is also provided a process for producing an organic amine, comprising the step of contacting an amination feedstock and an aminating agent with the catalyst as described above in the presence of hydrogen for an amination reaction.
[0152] According to a fourth type of embodiment of the present application, the aminating raw material or aminating agent can be selected as described above, and a detailed description thereof will be omitted herein for the sake of brevity.
[0153] According to a fourth type embodiment of the present application, the amination conditions are such that the molar ratio of hydrogen to the aminating agent to the amination raw material is 1 to 5:2 to 35:1, the temperature is 110 to 230°C, the pressure is 0.7 to 22 MPa, and the liquid phase volumetric space velocity of the amination raw material is 0.06 to 1 m 3 / (m 3 h).
[0154] Preferably, the amination raw material is a monohydric alcohol, and the amination conditions are a molar ratio of hydrogen to the aminating agent to the amination raw material of 1 to 4:2 to 8:1, a temperature of 130 to 210°C, a pressure of 1 to 2.5 MPa, and a liquid phase volumetric space velocity of the amination raw material of 0.1 to 0.8 m 3 / (m 3 h) is included.
[0155] Preferably, the amination raw material is a ketone or an aldehyde, and the amination conditions are a molar ratio of hydrogen to the aminating agent to the amination raw material of 1 to 4:2 to 5:1, a temperature of 110 to 180°C, a pressure of 0.7 to 2.5 MPa, and a liquid phase volumetric space velocity of the amination raw material of 0.1 to 0.8 m 3 / (m 3 h) is included.
[0156] Preferably, the amination raw material is an alcohol amine, and the amination conditions are a molar ratio of hydrogen to the aminating agent to the amination raw material of 1 to 4:3 to 23:1, a temperature of 130 to 200°C, a pressure of 1 to 16 MPa, and a liquid phase volumetric space velocity of the amination raw material of 0.06 to 0.8 m 3 / (m 3 h) is included.
[0157] Preferably, the amination raw material is a mixture of 1,6-hexanediol, cycloheximide, and 6-amino-1-hexanol, or a dihydric alcohol, and the amination conditions are a molar ratio of hydrogen to the aminating agent to the amination raw material of 1 to 4:3 to 35:1, a temperature of 130 to 230°C, a pressure of 1 to 22 MPa, and a liquid phase volumetric space velocity of the amination raw material of 0.1 to 0.8 m 3 / (m 3 h) is included.
[0158] In some preferred embodiments, the present application provides the following technical solutions: A1. A catalyst having a function of catalyzing the hydroamination of alcohols to produce organic amines, comprising a support, an active metal component supported on the support, and optionally a metal co-catalyst supported on the support, wherein the support comprises a matrix and a doping element, the matrix comprising an alumina support and optionally an additional support, the additional support being at least one selected from silica, molecular sieves, and diatomaceous earth; and a ratio of the ratio of pores having a pore diameter of less than 7.5 nm to the pore volume of the support. a ratio of the pore volume of pores having a pore diameter of less than 9 nm to the pore volume of the support is less than 20%, a ratio of the pore volume of pores having a pore diameter of more than 27 nm to the pore volume of the support is less than 40%, and a ratio of the pore volume of pores having a pore diameter of more than 27 nm to the pore volume of the support is less than 5%; the support has an ammonia adsorption capacity of 0.3 to 0.6 mmol / g; the support has an L acid content of 90% or more based on the total of the L acid content and the B acid content; and the active metal component is cobalt and / or nickel.
[0159] A2, the content of the alumina support in the matrix is 65% by weight or more, preferably 75% by weight or more, based on the total amount of the alumina support and the additional support; and / or the content of said doping element is 0.05-3 wt. %, preferably 0.08-2 wt. %, relative to the total weight of said matrix; and / or the doping element is derived from an acid radical ion other than a chloride ion, and the acid radical ion is at least one selected from the group consisting of non-metallic acid radical ions, preferably at least one selected from the group consisting of borate ions, fluoride ions, phosphate ions, sulfate ions and selenate ions; and / or the ratio of the pore volume of pores having a pore diameter of less than 7.5 nm to the pore volume of the support is 5 to 17%, the ratio of the pore volume of pores having a pore diameter of 7.5 nm or more and less than 9 nm to the pore volume of the support is 5 to 17%, the ratio of the pore volume of pores having a pore diameter of 9 nm or more and 27 nm or less to the pore volume of the support is 61 to 89.5%, and the ratio of the pore volume of pores having a pore diameter of more than 27 nm to the pore volume of the support is 0.5 to 5%; and / or the support has an ammonia adsorption capacity of 0.3 to 0.5 mmol / g; and / or the carrier has an L acid content of 92 to 100% based on the total of the L acid content and the B acid content; and / or the carrier is 105 to 220 m 2 / g specific surface area; and / or the support has a pore volume of 0.4 to 1.1 ml / g; And / or the catalyst according to item A1, wherein the content of the active metal component is 5 to 42 g, preferably 10 to 35 g, per 100 g of the matrix.
[0160] A3. The catalyst according to item A1 or A2, wherein the support is prepared by a method including successively shaping, drying, and calcining a mixture of a support modifier, pseudoboehmite, and optionally an additional support source, wherein the additional support source is at least one of a silica precursor, a molecular sieve precursor, and a diatomaceous earth precursor, and the calcination temperature is 800 to 1050°C.
[0161] A4. The catalyst according to item A3, wherein the support modifier is at least one selected from the group consisting of non-metallic acid radical ions, preferably at least one selected from borate ions, fluoride ions, phosphate ions, sulfate ions, and selenate ions.
[0162] A5, the carrier modifier is at least one selected from the group consisting of boric acid, nickel borate, cobalt borate, potassium borate, ammonium borate, potassium fluoride, cobalt fluoride, nickel fluoride, hydrofluoric acid, ammonium fluoride, phosphoric acid, aluminum phosphate, tripotassium phosphate, potassium dihydrogen phosphate, potassium hydrogen phosphate, magnesium phosphate, calcium phosphate, ammonium phosphate, sulfuric acid, cobalt sulfate, nickel sulfate, aluminum sulfate, calcium sulfate, potassium sulfate, magnesium sulfate, strontium phosphate, strontium sulfate, and selenic acid; And / or the pseudo-boehmite is 255 to 360 m 2 / g and a pore volume of 0.75 to 1.3 ml / g.
[0163] A6, the drying conditions include a temperature of 80 to 150°C and a drying time of 6 to 20 hours; And / or the catalyst according to any one of items A3 to A5, wherein the calcination conditions include a temperature of 800 to 1050°C and a calcination time of 2 to 20 hours.
[0164] A7. A method for producing the catalyst according to any one of items A1 to A6, comprising a step of supporting the active metal component and, optionally, the metal promoter on the support.
[0165] A8, a carrier as defined in any one of items A1 to A6.
[0166] A9: Use of the catalyst according to any one of items A1 to A6, or the method according to item A7, or the support according to item A8 in the production of an organic amine by amination.
[0167] A10, a process for producing an organic amine, comprising a step of contacting an amination raw material and an aminating agent with the catalyst according to any one of items A1 to A6 in the presence of hydrogen for an amination reaction; Or alternatively, the method includes the steps of screening a catalyst comprising a support defined in any one of items A1 to A6, and contacting an amination feedstock and an aminating agent with the screened catalyst in the presence of hydrogen for an amination reaction.
[0168] A11, the amination conditions are that the molar ratio of hydrogen to the aminating agent to the amination raw material is 1 to 5:2 to 35:1, the temperature is 110 to 220°C, the pressure is 1 to 25 MPa, and the liquid phase volumetric space velocity of the amination raw material is 0.06 to 1 m 3 / (m 3 h) including being; And / or, the amination raw material is at least one selected from the group consisting of C2 to C20 alcohols, C3 to C20 ketones, C2 to C20 alcoholamines, and C2 to C20 aldehydes, and is preferably ethanol, acetaldehyde, n-propanol, propionaldehyde, isopropanol, n-butanol, butyraldehyde, isobutanol, isobutyraldehyde, 2-ethylhexanol, 2-ethylhexaldehyde, octanol, octanal, dodecanol, dodecanal, hexadecanol, hexadecanal, cyclopentanol, cyclohexanol, cyclooctanol, or cyclooctanol. at least one of ethanol, cyclododecanol, benzyl alcohol, benzaldehyde, phenethyl alcohol, phenylacetaldehyde, 1,4-butanediol, 1,4-butanedial, 1,5-pentanediol, 1,5-glutaraldehyde, 1,6-hexanediol, 1,6-hexanedial, 1,8-octanediol, 1,8-octanedial, ethanolamine, propanolamine, isopropanolamine, 6-aminohexanol, diethanolamine, acetone, ethylene glycol, 1,3-propanediol, and 1,12-dodecanediol; And / or the method according to Item A10, wherein the aminating agent is at least one selected from the group consisting of ammonia, C1-C12 primary amines, and C1-C12 secondary amines, preferably at least one of ammonia, monomethylamine, dimethylamine, methylethylamine, monoethylamine, and diethylamine.
[0169] A12, the amination raw material is a monohydric alcohol, and the amination conditions are a molar ratio of hydrogen to the aminating agent to the amination raw material of 1 to 4:2 to 8:1, a temperature of 130 to 200°C, a pressure of 1 to 3.5 MPa, and a liquid phase volumetric space velocity of the amination raw material of 0.1 to 0.8 m 3 / (m 3 h) including being; Alternatively, when the amination raw material is a ketone or an aldehyde, the amination conditions are a molar ratio of hydrogen to the aminating agent to the amination raw material of 1 to 4:2 to 5:1, a temperature of 110 to 180°C, a pressure of 1 to 2.5 MPa, and a liquid phase volumetric space velocity of the amination raw material of 0.1 to 0.8 m 3 / (m 3 h) including being; Alternatively, when the amination raw material is an alcohol amine, the amination conditions are a molar ratio of hydrogen to the aminating agent to the amination raw material of 1 to 4:3 to 20:1, a temperature of 130 to 200°C, a pressure of 1 to 11 MPa, and a liquid phase volumetric space velocity of the amination raw material of 0.06 to 0.8 m 3 / (m 3 h) including being; Alternatively, when the amination raw material is a dihydric alcohol, the amination conditions are a molar ratio of hydrogen to the aminating agent to the amination raw material of 1 to 5:2 to 35:1, a temperature of 130 to 220°C, a pressure of 1 to 25 MPa, and a liquid phase volumetric space velocity of the amination raw material of 0.1 to 0.8 m 3 / (m 3 h) including being; Alternatively, when the amination raw material is a mixture of 1,6-hexanediol, hexamethyleneimine, and 6-amino-1-hexanol, the amination conditions are a molar ratio of hydrogen to the aminating agent to the amination raw material of 1 to 4:3 to 35:1, a temperature of 130 to 200°C, a pressure of 1 to 22 MPa, and a liquid phase volumetric space velocity of the amination raw material of 0.1 to 0.8 m 3 / (m 3 The method according to item A11, comprising: h).
[0170] B1. A catalyst having a function of catalyzing the production of amines from alcohols, comprising a support, an active metal component supported on the support, and optionally a metal co-catalyst supported on the support, wherein the support is at least one selected from the group consisting of doped alumina, doped silica, doped molecular sieve, and doped diatomaceous earth; the support has an ammonia adsorption capacity of 0.25 to 0.65 mmol / g; the support has an L acid content of 88% or more based on the total of the L acid content and the B acid content; the active metal component is cobalt and / or nickel, and the particle size of the active metal component in the catalyst is less than 10 nm.
[0171] B2. The support comprises a matrix selected from the group consisting of alumina, silica, molecular sieves and diatomaceous earth, and a doping element present in an amount of 0.05 to 5% by weight, preferably 0.08 to 4% by weight, relative to the total weight of the matrix; and / or the doping element in the carrier is derived from an acid radical ion other than a chloride ion; the acid radical ion is at least one selected from the group consisting of non-metallic acid radical ions, preferably at least one selected from the group consisting of borate ions, fluoride ions, phosphate ions, sulfate ions and selenate ions; and / or the support has an ammonia adsorption capacity of 0.3 to 0.5 mmol / g; and / or the carrier has an L acid content of 90 to 100% relative to the total of the L acid content and the B acid content; and / or the particle size of the active metal component in the catalyst is 3 to 8 nm; And / or the carrier is 100 to 200 m 2 / g specific surface area; and / or the support has a pore volume of 0.45 to 1 ml / g; and / or the carrier has an isoelectric point of 3 to 6, preferably 3.5 to 5.5; And / or the catalyst according to item B1, wherein the content of the active metal component is 7 to 45 g, preferably 12 to 38 g, per 100 g of the matrix.
[0172] B3. The catalyst according to item B1 or B2, wherein the support is prepared by a method comprising successively shaping, drying, and calcining a mixture containing doping ions and a precursor of a matrix, wherein the doping ions are provided by a support modifier, and the support modifier is at least one of an inorganic acid containing the doping ions and an inorganic salt containing the doping ions, and the calcination temperature is 800°C or higher.
[0173] B4. The catalyst according to item B3, wherein the inorganic acid is at least one selected from inorganic acids containing non-metallic acid radical ions, the inorganic salt is at least one selected from inorganic salts containing non-metallic acid radical ions, and the support modifier is preferably at least one selected from boric acid, potassium borate, magnesium borate, hydrofluoric acid, potassium fluoride, magnesium fluoride, phosphoric acid, potassium phosphate, magnesium phosphate, sulfuric acid, potassium sulfate, magnesium sulfate, and selenic acid.
[0174] B5, the precursor of the matrix is pseudo-boehmite, and the pseudo-boehmite has a viscosity of 260 to 400 m 2 / g and a pore volume of 0.75 to 1.2 ml / g.
[0175] B6, the drying conditions include a temperature of 80 to 150°C and a drying time of 6 to 20 hours; And / or the catalyst according to any one of Items B3 to B5, wherein the calcination conditions include a temperature of 820 to 1120°C and a calcination time of 2 to 20 hours.
[0176] B7. The method for producing the catalyst according to any one of Items B1 to B6, comprising the step of impregnating the support with an impregnation solution containing a precursor of an active metal component and a precursor of an optional metal promoter, so that the active metal component and the optional metal promoter are supported on the support, and the impregnation solution has a pH value in the range of 3.5 to 5.5.
[0177] B8, a carrier as defined in any one of items B1 to B6.
[0178] B9: Use of the catalyst according to any one of items B1 to B6, or the method according to item B7, or the support according to item B8, for the production of an organic amine by amination.
[0179] B10, for the amination reaction, comprising a step of contacting an amination raw material and an aminating agent with the catalyst according to any one of items B1 to B6 in the presence of hydrogen; Or alternatively, a process for producing an organic amine, the process comprising: screening a catalyst comprising the support according to any one of Items B1 to B6; and contacting an amination raw material and an aminating agent with the screened catalyst in the presence of hydrogen for an amination reaction.
[0180] B11, the amination conditions are that the molar ratio of hydrogen to the aminating agent to the amination raw material is 1 to 5:3 to 33:1, the temperature is 110 to 210°C, the pressure is 1 to 22 MPa, and the liquid phase volumetric space velocity of the amination raw material is 0.06 to 1 m 3 / (m 3 h) including being; and / or the amination raw material is at least one selected from the group consisting of C2 to C20 alcohols, C3 to C20 ketones, C2 to C20 alcoholamines, and C2 to C20 aldehydes, and is preferably ethanol, acetaldehyde, n-propanol, propionaldehyde, isopropanol, n-butanol, butylaldehyde, isobutanol, isobutylaldehyde, 2-ethylhexanol, 2-ethylhexaldehyde, octanol, octanal, dodecanol, dodecanal, hexadecanol, hexadecanal, cyclopentanol, cyclohexanol, cyclooctanol, or cyclododecanol. at least one of ethanol, benzyl alcohol, benzaldehyde, phenethyl alcohol, phenylacetaldehyde, 1,4-butanediol, 1,4-butanedial, 1,5-pentanediol, 1,5-glutaraldehyde, 1,6-hexanediol, 1,6-hexanedial, 1,8-octanedial, 1,8-octanedial, ethanolamine, propanolamine, isopropanolamine, 6-aminohexanol, diethanolamine, diisopropanolamine, dimethylethanolamine, acetone, ethylene glycol, 1,3-propanediol, and 1,12-dodecanediol; And / or the method according to Item B10, wherein the aminating agent is at least one selected from the group consisting of ammonia, C1-C12 primary amines, and C1-C12 secondary amines, preferably at least one of ammonia, monomethylamine, dimethylamine, methylethylamine, monoethylamine, and diethylamine.
[0181] B12: When the amination raw material is a monohydric alcohol, the amination conditions are a molar ratio of hydrogen to the aminating agent to the amination raw material of 1 to 4:2 to 8:1, a temperature of 130 to 200°C, a pressure of 0.8 to 2.5 MPa, and a liquid phase volumetric space velocity of the amination raw material of 0.1 to 0.8 m 3 / (m 3 h) including being; Alternatively, when the amination raw material is a ketone or an aldehyde, the amination conditions are a molar ratio of hydrogen to the aminating agent to the amination raw material of 1 to 4:2 to 6:1, a temperature of 110 to 170°C, a pressure of 1 to 2.5 MPa, and a liquid phase volumetric space velocity of the amination raw material of 0.1 to 0.8 m 3 / (m 3 h) including being; Alternatively, when the amination raw material is an alcohol amine, the amination conditions are a molar ratio of hydrogen to the aminating agent to the amination raw material of 1 to 4:3 to 10:1, a temperature of 130 to 200°C, a pressure of 1 to 11 MPa, and a liquid phase volumetric space velocity of the amination raw material of 0.06 to 0.8 m 3 / (m 3 h) including being; Alternatively, when the amination raw material is a mixture of 1,6-hexanediol, hexamethyleneimine, and 6-amino-1-hexanol or a dihydric alcohol, the amination conditions are a molar ratio of hydrogen to the aminating agent to the amination raw material of 1 to 4:3 to 33:1, a temperature of 130 to 210°C, a pressure of 1 to 22 MPa, and a liquid phase volumetric space velocity of the amination raw material of 0.1 to 0.8 m 3 / (m 3 The method according to item B11, comprising: h).
[0182] C1. A catalyst having a function of producing an amine by the hydroamination of an alcohol, comprising: a support; an active metal component supported on the support; and optionally a metal co-catalyst supported on the support, wherein the support comprises a matrix and a doping element, the matrix comprising an alumina support and optionally an additional support, the additional support being selected from silica and / or molecular sieves, and the doping element being at least one selected from the group consisting of boron, fluorine, phosphorus, sulfur, and selenium; the ratio of the pore volume of pores having a pore diameter in the range of 7 to 27 nm to the pore volume of the support is more than 65%; and the active metal component is cobalt and / or nickel.
[0183] C2. The content of the alumina support in the support matrix is 70% by weight or more, preferably 75 to 100% by weight; and / or the content of said doping element in said support is 0.05-6 wt. %, preferably 0.08-4 wt. %, relative to the total weight of said matrix; and / or said doping element is incorporated in the form of at least one selected from the group consisting of borate, fluoride, phosphate, sulfate and selenate ions; and / or the ratio of the pore volume of pores having a pore diameter in the range of 7 to 27 nm to the pore volume of the support is more than 65%, preferably the ratio of the pore volume of pores having a pore diameter in the range of 7 to 27 nm to the pore volume of the support is 70 to 90%, and the ratio of the pore volume of pores having a pore diameter of less than 7 nm to the pore volume of the support is 0 to 10%; and / or the carrier has an L acid content of 85% or more, preferably 85 to 98%, based on the total of the L acid content and the B acid content; And / or the carrier is 120 to 210 m 2 / g specific surface area; and / or the support has a pore volume of 0.43 to 1.1 ml / g; And / or the catalyst according to item C1, wherein the content of the active metal component is 8 to 44 g, preferably 12 to 37 g, per 100 g of the matrix.
[0184] C3. The catalyst according to item C1 or C2, wherein the support is prepared by a method comprising successively shaping, drying and calcining a mixture comprising the doping element and a precursor of the support, wherein the precursor of the support is selected from a precursor of alumina and optionally a precursor of an additional matrix, and the precursor of the additional matrix is selected from a precursor of silica and / or a precursor of a molecular sieve.
[0185] C4. The catalyst according to item C3, wherein the doping element is provided by at least one selected from compounds containing non-metallic acid radical ions, preferably at least one selected from compounds containing borate ions, compounds containing fluoride ions, compounds containing phosphate ions, compounds containing sulfate ions, and compounds containing selenate ions.
[0186] C5, the alumina precursor is pseudoboehmite, and the pseudoboehmite has a content of 255 to 340 m 2 The catalyst according to item C3 or C4, having a specific surface area of 0.78 to 1.25 ml / g and a pore volume of 0.78 to 1.25 ml / g.
[0187] C6, the drying conditions include a temperature of 80 to 150°C and a drying time of 6 to 20 hours; And / or the catalyst according to any one of items C3 to C5, wherein the calcination conditions include a temperature of 700 to 1100°C and a calcination time of 2 to 20 hours.
[0188] C7. A method for producing the catalyst according to any one of items C1 to C6, comprising supporting the active metal component and optionally the metal promoter on the support.
[0189] C8, a carrier as defined in any one of items C1 to C6.
[0190] C9: Use of the catalyst according to any one of items C1 to C6, or the method according to item C7, or the support according to item C8, for producing an organic amine by amination.
[0191] C10, for the amination reaction, comprising contacting an amination raw material and an aminating agent with the catalyst according to any one of items C1 to C6 in the presence of hydrogen; Or alternatively, a process for producing an organic amine, comprising: screening a catalyst comprising a support defined in any one of items C1 to C6; and contacting an amination raw material and an aminating agent with the screened catalyst in the presence of hydrogen for an amination reaction.
[0192] C11, the amination conditions are that the molar ratio of hydrogen to the aminating agent to the amination raw material is 1 to 6:2 to 32:1, the temperature is 105 to 210°C, the pressure is 1 to 17 MPa, and the liquid phase volumetric space velocity of the amination raw material is 0.06 to 1 m 3 / (m 3 h) including being; and / or the amination raw material is at least one selected from the group consisting of C2 to C20 alcohols, C3 to C20 ketones, C2 to C20 alcoholamines, and C2 to C20 aldehydes, and is preferably ethanol, acetaldehyde, n-propanol, propionaldehyde, isopropanol, n-butanol, butylaldehyde, isobutanol, isobutylaldehyde, 2-ethylhexanol, 2-ethylhexaldehyde, octanol, octanal, dodecanol, dodecanal, hexadecanol, hexadecanal, cyclopentanol, cyclohexanol, cyclooctanol, or cyclododecanol. at least one of ethanol, benzyl alcohol, benzaldehyde, phenethyl alcohol, phenylacetaldehyde, 1,4-butanediol, 1,4-butanedial, 1,5-pentanediol, 1,5-glutaraldehyde, 1,6-hexanediol, 1,6-hexanedial, 1,8-octanedial, 1,8-octanedial, ethanolamine, propanolamine, isopropanolamine, 6-aminohexanol, diethanolamine, diisopropanolamine, dimethylethanolamine, acetone, ethylene glycol, 1,3-propanediol, and 1,12-dodecanediol; And / or the process according to item C10, wherein the aminating agent is at least one selected from the group consisting of ammonia, C1-C12 primary amines and C1-C12 secondary amines, preferably at least one of ammonia, monomethylamine, dimethylamine, methylethylamine, monoethylamine and diethylamine.
[0193] C12, when the amination raw material is a monohydric alcohol, the amination conditions are a molar ratio of hydrogen to the aminating agent to the amination raw material of 1 to 4:2 to 9:1, a temperature of 130 to 208°C, a pressure of 1 to 2.5 MPa, and a liquid phase volumetric space velocity of the amination raw material of 0.1 to 0.8 m 3 / (m 3 h) including being; Alternatively, when the amination raw material is a ketone or an aldehyde, the amination conditions are a molar ratio of hydrogen to the aminating agent to the amination raw material of 1 to 4:2 to 5:1, a temperature of 105 to 160°C, a pressure of 1 to 2 MPa, and a liquid phase volumetric space velocity of the amination raw material of 0.1 to 1 m 3 / (m 3 h) including being; Alternatively, when the amination raw material is an alcohol amine, the amination conditions are a molar ratio of hydrogen to the aminating agent to the amination raw material of 1 to 4:3 to 20:1, a temperature of 130 to 200°C, a pressure of 1 to 13 MPa, and a liquid phase volumetric space velocity of the amination raw material of 0.06 to 0.8 m 3 / (m 3 h) including being; Alternatively, when the amination raw material is a mixture of 1,6-hexanediol, hexamethyleneimine, and 6-amino-1-hexanol or a dihydric alcohol, the amination conditions are a molar ratio of hydrogen to the aminating agent to the amination raw material of 1 to 4:3 to 32:1, a temperature of 130 to 210°C, a pressure of 1 to 17 MPa, and a liquid phase volumetric space velocity of the amination raw material of 0.1 to 0.9 m 3 / (m 3The process according to item C11, comprising: h).
[0194] D1. A catalyst having the function of catalyzing the production of amines from alcohols, comprising a support, an active metal component supported on the support, and a metal cocatalyst supported on the support, wherein the active metal component is cobalt and / or nickel; and the metal cocatalyst is a combination of at least one Group IIA metal, at least one Group IIB metal, and at least one Group VA metal.
[0195] D2. The catalyst according to item D1, wherein the support comprises a matrix and a doping element, the matrix comprising an alumina support and optionally an additional support, the additional support comprising silica and / or a molecular sieve; the doping element is at least one selected from the group consisting of boron, fluorine, phosphorus, sulfur, and selenium; and the ratio of the pore volume of pores having a pore diameter in the range of 7 to 27 nm to the pore volume of the support is more than 65%.
[0196] D3, the content of the alumina support in the support matrix is 70% by weight or more, preferably 75 to 100% by weight, based on the total amount of the alumina support and the additional support; and / or the content of the doping element in the support is 0.05-4.5 wt. %, preferably 0.07-2.8 wt. %, relative to the total weight of the matrix; and / or said doping element in said carrier is incorporated in the form of at least one selected from the group consisting of borate ions, fluoride ions, phosphate ions, sulfate ions and selenate ions; and / or the ratio of the pore volume of pores having a pore diameter in the range of 7 to 27 nm to the pore volume of the support is 70 to 90%, and the ratio of the pore volume of pores having a pore diameter of less than 7 nm to the pore volume of the support is 0 to 8%; And / or the carrier is 110 to 210 m 2 / g specific surface area; and / or the support has a pore volume of 0.45 to 1.1 ml / g; and / or the content of the active metal component is 8 to 45 g, preferably 15 to 38 g, per 100 g of the matrix; and / or the metal promoter is present in an amount of 0.1 to 10 g, preferably 0.5 to 6 g, per 100 g of the matrix; and / or the weight ratio of the Group IIA metal, the Group IIB metal, and the Group VA metal in the metal co-catalyst is 0.1-10:0.1-10:1, preferably 0.2-8:0.2-8:1; and / or said Group IIA metal is at least one selected from the group consisting of magnesium, calcium and barium; and / or said Group IIB metal is selected from zinc; and / or said Group VA metal is selected from bismuth.
[0197] D4. The catalyst according to item D2 or D3, wherein the support is prepared by a method comprising the following steps (1) and (2): (1) sequentially shaping, first drying and first calcining a mixture comprising a doping element, an alumina precursor and, optionally, an additional support precursor, wherein the additional support precursor comprises a silica precursor and / or a molecular sieve precursor; (2) mixing the product of the first calcination with a solution of a Group IIA metal precursor, followed by a second drying and a second calcination.
[0198] D5, the alumina precursor is pseudoboehmite, and the pseudoboehmite has a content of 250 to 330 m 2 / g specific surface area, 0.5-1.1 ml / g pore volume; and / or the conditions of the first firing include a temperature of 500 to 650°C and a firing time of 2 to 20 hours; And / or the catalyst according to item D4, wherein the conditions of the second calcination include a temperature of 800 to 1100°C and a calcination time of 2 to 20 hours.
[0199] D6: A method for producing the catalyst according to any one of D1 to D5, which includes the following (1) to (3): (1) sequentially shaping, first drying and first calcining a mixture comprising a doping element, an alumina precursor and, optionally, an additional support precursor, wherein the additional support precursor comprises a silica precursor and / or a molecular sieve precursor; (2) mixing the product of the first calcination with a solution of a Group IIA metal precursor, followed by a second drying and second calcination; (3) supporting at least one Group IIB metal, at least one Group VA metal, and an active metal component on the product of the second calcination.
[0200] D7, a carrier as defined in any one of items D1 to D5.
[0201] D8: Use of the catalyst according to any one of items D1 to D5, or the method according to item D6, or the support according to item D7, for producing an organic amine by amination.
[0202] D9, for an amination reaction, comprising contacting an amination feedstock and an aminating agent with the catalyst described in any one of items D1 to D5 in the presence of hydrogen; Or alternatively, the method for producing an organic amine includes the steps of: screening a catalyst comprising a support defined in any one of items D1 to D5; and contacting an amination raw material and an aminating agent with the screened catalyst in the presence of hydrogen for an amination reaction.
[0203] D10, the amination conditions are that the molar ratio of hydrogen to the aminating agent to the amination raw material is 1 to 5:2 to 35:1, the temperature is 110 to 230°C, the pressure is 0.7 to 22 MPa, and the liquid phase volumetric space velocity of the amination raw material is 0.06 to 1 m 3 / (m 3 h) including being; and / or the amination raw material is at least one selected from the group consisting of C2 to C20 alcohols, C3 to C20 ketones, C2 to C20 alcoholamines, and C2 to C20 aldehydes, and is preferably ethanol, acetaldehyde, n-propanol, propionaldehyde, isopropanol, n-butanol, butylaldehyde, isobutanol, isobutylaldehyde, 2-ethylhexanol, 2-ethylhexaldehyde, octanol, octanal, dodecanol, dodecanal, hexadecanol, hexadecanal, cyclopentanol, cyclohexanol, cyclooctanol, or cyclododecanol. at least one of ethanol, benzyl alcohol, benzaldehyde, phenethyl alcohol, phenylacetaldehyde, 1,4-butanediol, 1,4-butanedial, 1,5-pentanediol, 1,5-glutaraldehyde, 1,6-hexanediol, 1,6-hexanedial, 1,8-octanedial, 1,8-octanedial, ethanolamine, propanolamine, isopropanolamine, 6-aminohexanol, diethanolamine, diisopropanolamine, dimethylethanolamine, acetone, ethylene glycol, 1,3-propanediol, and 1,12-dodecanediol; And / or the method according to Item D9, wherein the aminating agent is at least one selected from the group consisting of ammonia, C1-C12 primary amines, and C1-C12 secondary amines, and preferably at least one of ammonia, monomethylamine, dimethylamine, methylethylamine, monoethylamine, and diethylamine.
[0204] D11, when the amination raw material is a monohydric alcohol, the amination conditions are a molar ratio of hydrogen to the aminating agent to the amination raw material of 1 to 4:2 to 8:1, a temperature of 130 to 210°C, a pressure of 1 to 2.5 MPa, and a liquid phase volumetric space velocity of the amination raw material of 0.1 to 0.8 m 3 / (m 3 h) including being; Alternatively, when the amination raw material is a ketone or an aldehyde, the amination conditions are a molar ratio of hydrogen to the aminating agent to the amination raw material of 1 to 4:2 to 5:1, a temperature of 110 to 180°C, a pressure of 0.7 to 2.5 MPa, and a liquid phase volumetric space velocity of the amination raw material of 0.1 to 0.8 m 3 / (m 3 h) including being; Alternatively, when the amination raw material is an alcohol amine, the amination conditions are a molar ratio of hydrogen to the aminating agent to the amination raw material of 1 to 4:3 to 23:1, a temperature of 130 to 200°C, a pressure of 1 to 16 MPa, and a liquid phase volumetric space velocity of the amination raw material of 0.06 to 0.8 m 3 / (m 3 h) including being; Alternatively, when the amination raw material is a mixture of 1,6-hexanediol, hexamethyleneimine, and 6-amino-1-hexanol or a dihydric alcohol, the amination conditions are a molar ratio of hydrogen to the aminating agent to the amination raw material of 1 to 4:3 to 35:1, a temperature of 130 to 230°C, a pressure of 1 to 22 MPa, and a liquid phase volumetric space velocity of the amination raw material of 0.1 to 0.8 m 3 / (m 3 The method according to item D10, comprising: h).
[0205] [Example] The present application is further illustrated by, but not limited to, the following examples.
[0206] The test equipment and methods used in the following examples are as follows: 1) NH3-TPD test Test equipment: Autochem 2920 fully automatic chemisorption instrument (automated catalyst characterization system), manufactured by MICROMERITICS, USA; Test conditions: Approximately 0.1 g of sample was accurately weighed and placed in a sample tube. While purging with helium gas, the tube was heated to 600°C at a rate of 10°C / min, held for 1 hour, and then cooled to 120°C. The gas was then switched to a 10% NH3-He mixed gas and allowed to adsorb for 60 minutes. After that, the gas was switched back to helium gas and purged for 1 hour. After the baseline stabilized, counting began. The resulting material was heated to 600°C at a rate of 10°C / min, held for 30 minutes, and recording was stopped to terminate the test. The peak area was integrated to determine the amount of NH3 desorption, which was used to characterize the ammonia adsorption capacity of the sample.
[0207] 2) BET test Testing equipment: ASAP2420 fully automatic physicochemical adsorption analyzer (automated micropore & chemical adsorption analyzer), manufactured by MICROMERITICS, USA; Test conditions: Test gas: N2 (purity 99.999%); Degassing conditions: Heat to 350 °C at a rate of 10 °C / min and evacuate for 4 hours; Analysis conditions: Obtain the specific surface area and pore volume by fully analyzing the mesopore isotherm.
[0208] 3) Probe adsorption spectroscopy Test equipment: NICOLET 6700 infrared spectrometer with in-situ transmission cell, available from Thermo Scientific; Test conditions: The sample was accurately weighed and its mass was recorded. The sample was heated to 500°C at a heating rate of 10°C / min under vacuum conditions. The support was pretreated at this temperature for 2 hours and then cooled to room temperature. Pyridine vapor was adsorbed onto the pretreated support until it was saturated at room temperature. The support was then statically desorbed to an equilibrium state under vacuum conditions at room temperature, 100°C, 150°C, 200°C, 300°C, and 400°C, with a heating rate of 10°C / min between each temperature point.
[0209] 4)XRD analysis Test equipment: Empyrean X-ray diffractometer manufactured by PANalytical BV with a Cu target anode target and a Pixcel 3D detector; Test conditions: tube voltage 40 kV, tube current 40 mA, divergence slit 1 / 4°, anti-divergence slit 1 / 2°, receiving slit height 7.5 mm, scanning speed 0.013° / step, scanning range 5°~90°.
[0210] The particle sizes of the active metal components and metal promoters, if present, were obtained by calculation using the Scherrer equation.
[0211] 5) Isoelectric point test Test equipment: Zetasizer Nano ZSP particle size potentiometer available from Malvern Panalytical Company; Test method: The sample was crushed into powder and dispersed in a low concentration NaCl solution. The zeta potential of the sample was measured at various pH values using a particle size potentiometer, and then plotted against pH. The pH value at which the zeta potential was 0 is the isoelectric point of the sample.
[0212] In the following examples and comparative examples, unless otherwise specified, the agents and starting materials used are analytically pure, commercially available products.
[0213] Example Series I The first type of embodiment of the present application will be described in more detail below with reference to examples in Example Series I. In the following examples in Example Series I, the pseudoboehmite powder has an (Al2O3) content of 72 wt % on a dry basis, and the silica sol was purchased from Qingdao Ocean Chemical Co., Ltd. under the trade name JN-40.
[0214] Example I-1 Pseudoboehmite powder (315m 2 / g specific surface area and pore volume of 0.91 mL / g) was kneaded with a dilute acid aqueous solution containing nitric acid and boric acid, extruded into strips with a diameter of 5 mm, cut into 4 mm lengths, dried at 100°C for 10 hours, and calcined at 850°C for 4 hours to obtain the desired support. The amount of boric acid was adjusted to obtain the boron content in the support as shown in Table I-1.
[0215] 151.2 g of cobalt nitrate hexahydrate (technical grade, 98% purity) was dissolved in water to obtain 184 mL of solution. The solution was twice supported on 100 g of the obtained support by spray impregnation. After each spray impregnation, it was dried at 120 ° C for 4 hours, then calcined at 400 ° C for 4 hours, and then reduced with hydrogen while gradually increasing the temperature at a rate of 20 ° C / hour, and finally reduced at 430 ° C for 3 hours to obtain catalyst CI-1. The particle size of the supported component measured by XRD was 20 nm (a detailed description of which can be found in Test Example I-1).
[0216] Example I-2 Silica sol was mixed with pseudoboehmite powder (322 ml) in a kneader. 2 The resulting mixture was added to a silica sol (having a specific surface area of 0.57 m / g and a pore volume of 0.93 mL / g) and uniformly kneaded. The mixture was then kneaded with a dilute aqueous acid solution containing nitric acid and hydrofluoric acid, extruded into cloverleaf-shaped granules with a thickness of 3 mm, dried at 120°C for 6 hours, and calcined at 820°C for 3.5 hours to obtain the desired support. The amount of hydrofluoric acid was adjusted to obtain the fluorine content in the support as shown in Table I-1. The amount of silica sol was adjusted so that the mass ratio of SiO2 to Al2O3 in the support was 9:1.
[0217] 177 g of nickel nitrate hexahydrate (technical grade, 98% purity) was dissolved in water to obtain 172 mL of solution, and 3.7 g of ammonium molybdate tetrahydrate (analytical purity) was dissolved in water to obtain 86 mL of solution. The nickel nitrate solution was supported twice on 100 g of the resulting support by spray impregnation; the ammonium molybdate solution was supported once on the support by spray impregnation. After each spray impregnation, the support was dried at 120 °C for 4 hours and calcined at 390 °C for 4 hours, then reduced with hydrogen while gradually increasing the temperature at a rate of 20 °C / hour, and finally reduced at 440 °C for 3 hours to obtain catalyst CI-2. The particle size of the supported components measured by XRD was 22 nm.
[0218] Example I-3 Silica sol was mixed with pseudoboehmite powder (345 m 2 The silica sol was added to a sol having a specific surface area of 0.05 µm / g and a pore volume of 1.12 mL / g, mixed uniformly, kneaded with a dilute acid solution containing nitric acid and phosphoric acid, extruded into toothed spheres with a diameter of 4 mm, dried at 80°C for 20 hours, and then calcined at 800°C for 4 hours to obtain the desired support. The amount of phosphoric acid was adjusted to obtain the P content in the support as shown in Table I-1. The amount of silica sol was adjusted so that the mass ratio of SiO2 to Al2O3 in the support was 3:1.
[0219] 50.4 g of cobalt nitrate hexahydrate (technical grade, 98% purity), 19.5 g of a 50 wt % manganese nitrate solution, and 8.5 g of copper nitrate trihydrate (analytical purity) were dissolved in water to obtain 158 mL of solution. The mixed solution was supported on 100 g of the resulting support twice by spray impregnation. After each spray impregnation, the support was dried at 120 °C for 4 hours, then calcined at 395 °C for 4 hours, and then reduced with hydrogen while gradually increasing the temperature at a rate of 20 °C / hour. Finally, the support was reduced at 430 °C for 3 hours to obtain catalyst CI-3. The particle size of the supported component measured by XRD was 15 nm.
[0220] Example I-4 Pseudoboehmite powder (350m 2 diatomaceous earth powder (57 m2 The resulting mixture was mixed with a sintered silicate (having a specific surface area of 0.1 / g), kneaded with a dilute aqueous solution of nitric acid and sulfuric acid, extruded into strips with a diameter of 5 mm, cut into 4 mm lengths, dried at 150°C for 6 hours, and calcined at 880°C for 4 hours to obtain the desired support. The amount of sulfuric acid was adjusted to obtain the sulfur content in the support as shown in Table I-1. The amount of diatomaceous earth was adjusted so that the mass ratio of Al2O3 to SiO2 in the support was 19:1.
[0221] 126.4 g of nickel nitrate hexahydrate (technical grade, 98% purity) was dissolved in water to obtain 176 mL of solution. The mixed solution was supported on 100 g of the obtained support twice by spray impregnation. After each spray impregnation, it was dried at 120 °C for 4 hours, then calcined at 380 °C for 4.5 hours, and then reduced with hydrogen while gradually increasing the temperature at a rate of 20 °C / hour. Finally, it was reduced at 430 °C for 3 hours to obtain catalyst CI-4. The particle size of the supported component measured by XRD was 22 nm.
[0222] Example I-5 Pseudoboehmite powder (320m 2 / g specific surface area and pore volume of 0.9 mL / g) was kneaded with a dilute acid aqueous solution containing nitric acid and sulfuric acid, extruded into cloverleaf-shaped granules with a thickness of 3 mm, dried at 120°C for 8 hours, and then calcined at 890°C for 4.5 hours to obtain the desired carrier, and the amount of sulfuric acid was adjusted to obtain the content of S element in the carrier as shown in Table I-1.
[0223] 40.4 g of nickel nitrate hexahydrate (technical grade, 98% purity), 60.5 g of cobalt nitrate hexahydrate (technical grade, 98% purity), and 2.9 g of ammonium perrhenate (99% purity) were dissolved in 186 mL of water. The mixed solution was supported on 100 g of the resulting support by spray impregnation twice. After each spray impregnation, the support was dried at 100 °C for 6 hours and then calcined at 390 °C for 4 hours. Hydrogen was reduced while gradually increasing the temperature at a rate of 20 °C / hour, and finally reduced at 440 °C for 3 hours to obtain catalyst CI-5. The particle size of the supported component measured by XRD was 16 nm.
[0224] Example I-6 Pseudoboehmite powder (312m 2 The desired support was obtained by mixing a sieve powder (ZSM-5 type, available from the Catalyst Factory of Nankai University, with a SiO2 / Al2O3 molar ratio of 45) with a dilute aqueous solution containing nitric acid and selenic acid. The resulting mixture was extruded into 4 mm diameter toothed spheres, dried at 120°C for 8 hours, and calcined at 810°C for 6 hours. The amount of selenic acid was adjusted to obtain the Se content in the support as shown in Table I-1. The amount of molecular sieve was adjusted so that the mass ratio of SiO2 to Al2O3 in the support was 94:6.
[0225] 126 g of cobalt nitrate hexahydrate (technical grade, 98% purity) was dissolved in water to obtain 152 mL of solution. The mixed solution was supported on 100 g of the obtained support twice by spray impregnation. After each spray impregnation, it was dried at 120 °C for 5 hours and then calcined at 400 °C for 3.5 hours. It was then reduced with hydrogen while gradually increasing the temperature at a rate of 20 °C / hour, and finally reduced at 430 °C for 3 hours to obtain catalyst CI-6. The particle size of the supported component measured by XRD was 25 nm.
[0226] Example I-7 Pseudoboehmite powder (348m 2 The resulting granules (having a specific surface area of 1.13 mL / g and a pore volume of 1.13 mL / g) were kneaded with a dilute aqueous solution of nitric acid and boric acid, extruded into toothed spheres with a diameter of 4 mm, dried at 100°C for 8 hours, and then calcined at 950°C for 6.5 hours to obtain the desired support. The amount of boric acid used was adjusted to obtain the B element content in the support as shown in Table I-1.
[0227] 100.8 g of cobalt nitrate hexahydrate (technical grade, 98% purity) and 1.3 g of silver nitrate (analytical purity) were dissolved in water to obtain 170 mL of solution. The mixed solution was supported on 100 g of the obtained support twice by spray impregnation. After each spray impregnation, the support was dried at 120 °C for 4 hours, then calcined at 400 °C for 4 hours, and then reduced with hydrogen while gradually increasing the temperature at a rate of 20 °C / hour. Finally, the support was reduced at 410 °C for 3 hours to obtain catalyst CI-7. The particle size of the supported component measured by XRD was 11 nm.
[0228] Example I-8 Pseudo-boehmite powder (356m 2 The carrier (having a specific surface area of 1.2 mL / g and a pore volume of 1.2 mL / g) was kneaded with a dilute acid solution containing nitric acid, sulfuric acid, and phosphoric acid, extruded into toothed spheres with a diameter of 3 mm, dried at 100°C for 8 hours, and then calcined at 860°C for 4 hours to obtain the desired carrier. The amounts of phosphoric acid and sulfuric acid used were adjusted to obtain the P and S element contents in the carrier as shown in Table I-1.
[0229] 141.6 g of nickel nitrate hexahydrate (technical grade, 98% purity) and 3.1 g of cerium nitrate hexahydrate (analytical purity) were dissolved in water to obtain 184 mL of solution. The mixed solution was supported on 100 g of the obtained support twice by spray impregnation. After each spray impregnation, the support was dried at 120 °C for 5 hours, then calcined at 410 °C for 4 hours, and then reduced with hydrogen while gradually increasing the temperature at a rate of 20 °C / hour. Finally, the support was reduced at 400 °C for 3 hours to obtain catalyst CI-8. The particle size of the supported component measured by XRD was 12 nm.
[0230] Example I-9 Silica sol was mixed with pseudoboehmite powder (315 m 2The silica sol was added to a sol (having a specific surface area of 0.57 / g and a pore volume of 0.88 mL / g) in a kneader, mixed uniformly, kneaded with a dilute acid solution containing nitric acid and sulfuric acid, extruded into toothed spheres with a diameter of 3 mm, dried at 100°C for 8 hours, and calcined at 900°C for 6 hours to obtain the desired support. The amount of sulfuric acid was adjusted to obtain the sulfur element content in the support as shown in Table I-1. The amount of silica sol was adjusted so that the mass ratio of SiO2 to Al2O3 in the support was 72:28.
[0231] 100.8 g of cobalt nitrate hexahydrate (technical grade, 98% purity) and 50.6 g of nickel nitrate hexahydrate (technical grade, 98% purity) were dissolved in water to obtain 146 mL of solution. The mixed solution was supported on 100 g of the obtained support twice by spray impregnation. After each spray impregnation, the support was dried at 100 °C for 8 hours and then calcined at 420 °C for 4 hours. The support was then reduced with hydrogen while gradually increasing the temperature at a rate of 20 °C / hour, and finally reduced at 410 °C for 3 hours to obtain catalyst CI-9. The particle size of the supported component measured by XRD was 18 nm.
[0232] Example I-10 Silica sol was mixed with pseudoboehmite powder (292 m 2 The silica sol was added to a solution of 10 ...
[0233] 201.6 g of cobalt nitrate hexahydrate (technical grade, 98% purity) and 6.2 g of lanthanum nitrate hexahydrate (analytical purity) were dissolved in water to obtain 165 mL of solution. The mixed solution was supported on 100 g of the obtained support three times by spray impregnation. After each spray impregnation, it was dried at 120 °C for 6 hours, then calcined at 420 °C for 4 hours, and then reduced with hydrogen while gradually increasing the temperature at a rate of 20 °C / hour. Finally, it was reduced at 410 °C for 3 hours to obtain catalyst CI-10. The particle size of the supported component measured by XRD was 13 nm.
[0234] Example I-11 Pseudoboehmite powder (276m 2 / g specific surface area and pore volume of 0.79 mL / g) was kneaded with a dilute acid solution containing nitric acid and sulfuric acid, extruded into cloverleaf-shaped granules with a thickness of 4 mm, dried at 110°C for 6 hours, and then calcined at 930°C for 6 hours to obtain the desired carrier. The amount of sulfuric acid was adjusted to obtain the sulfur element content in the carrier as shown in Table I-1.
[0235] 15.2 g of nickel nitrate hexahydrate (technical grade, 98% purity), 25.2 g of cobalt nitrate hexahydrate (technical grade, 98% purity), and 4.4 g of ammonium perrhenate (99% purity) were dissolved in water to obtain 176 mL of solution. The mixed solution was supported on 100 g of the resulting support twice by spray impregnation. After each spray impregnation, the support was dried at 120 °C for 4 hours and then calcined at 390 °C for 5 hours. The catalyst was then reduced with hydrogen while gradually increasing the temperature at a rate of 20 °C / hour, and finally reduced at 440 °C for 3 hours to obtain catalyst CI-11. The particle size of the supported component measured by XRD was 19 nm.
[0236] Example I-12 Pseudoboehmite powder (260m 2 / g specific surface area and pore volume of 0.77 mL / g) was kneaded with a dilute acid aqueous solution containing nitric acid and phosphoric acid, extruded into cloverleaf-shaped granules with a thickness of 4 mm, dried at 100°C for 12 hours, and then calcined at 860°C for 9 hours to obtain the desired carrier. The amount of phosphoric acid was adjusted to obtain the P element content in the carrier as shown in Table I-1.
[0237] 100.8 g of cobalt nitrate hexahydrate (technical grade, 98% purity) and 14.1 g of copper nitrate trihydrate (analytical purity) were dissolved in water to obtain 180 mL of solution. The mixed solution was supported on 100 g of the obtained support twice by spray impregnation. After each spray impregnation, it was dried at 120 °C for 4 hours and then calcined at 390 °C for 5 hours. After that, it was reduced with hydrogen while gradually increasing the temperature at a rate of 20 °C / hour, and finally reduced at 440 °C for 3 hours to obtain catalyst CI-12. The particle size of the supported component measured by XRD was 21 nm.
[0238] Example I-13 Pseudoboehmite powder (257m 2 / g specific surface area and pore volume of 0.76 mL / g) was kneaded with a dilute acid solution containing nitric acid and boric acid, extruded into cloverleaf-shaped granules with a thickness of 3 mm, dried at 120°C for 8 hours, and then calcined at 850°C for 6 hours to obtain the desired support. The amount of boric acid was adjusted to obtain the B element content in the support as shown in Table I-1.
[0239] 151.7 g of nickel nitrate hexahydrate (technical grade, 98% purity) and 12.5 g of lanthanum nitrate hexahydrate (analytical purity) were dissolved in water to obtain 184 mL of solution. The mixed solution was supported on 100 g of the resulting support twice by spray impregnation. After each spray impregnation, the support was dried at 120 °C for 4 hours, then calcined at 370 °C for 6 hours, and then reduced with hydrogen while gradually increasing the temperature at a rate of 20 °C / hour. Finally, the support was reduced at 430 °C for 4 hours to obtain catalyst CI-13. The particle size of the supported component measured by XRD was 12 nm.
[0240] Example I-14 Catalyst CI-14 was prepared as described in Example I-5, except that sulfuric acid was added so that the content of S element in the support was as shown in Table I-1. The particle size of the supported component measured by XRD was 16 nm.
[0241] Example I-15 Catalyst CI-15 was prepared as described in Example I-5, except that the temperature for calcining the support was 800° C. and the calcination time was 2 hours. The particle size of the supported component measured by XRD was 14 nm.
[0242] Example I-16 A catalyst was prepared as described in Example I-5, except that the silica sol was added while kneading so that the mass ratio of SiO to AlO in the support was 66:34, to obtain catalyst CI-16. The particle size of the supported component measured by XRD was 16 nm.
[0243] Example I-17 ZSM-5 (338m 2 The desired carrier was obtained by kneading a sintered silica (having a specific surface area of 0.61 mL / g, a pore volume of 0.61 mL / g, a crystallinity of 97.9%, and a SiO2 / Al2O3 = 60) with a dilute aqueous acid solution containing nitric acid, sulfuric acid, and phosphoric acid, extruding it into toothed spheres with a diameter of 3 mm, drying it at 120°C for 6 hours, and then calcining it at 880°C for 4 hours. The amounts of phosphoric acid and sulfuric acid were adjusted to obtain the P and S element contents in the carrier as shown in Table I-1.
[0244] Catalyst impregnation was carried out as described in Example I-8 to obtain catalyst CI-17. The particle size of the supported component measured by XRD was 14 nm.
[0245] Comparative example I-1 A catalyst was prepared in the same manner as in Example I-12, except that in the preparation of the support, the calcination temperature was 700° C. and the calcination time was 5 hours, to obtain catalyst DI-1.
[0246] Comparative example I-2 A catalyst was prepared in the same manner as in Example I-12, to obtain catalyst DI-2, except that in the preparation of the carrier, the calcination temperature was 550°C, the calcination time was 3 hours, and the amount of phosphoric acid used was adjusted to obtain the P element content in the carrier as shown in Table I-1.
[0247] Test Example I-1 The elemental composition of the support and catalyst was analyzed by plasma emission spectroscopy, and the content of elements (ions) other than the support was expressed as the content of the elements per 100 g of matrix, i.e., the content of the support calculated based on the components other than the doping elements (for example, when pseudoboehmite is used as the support raw material, it is calculated based on Al2O3); the obtained support was characterized by probe adsorption spectroscopy (characterizing the ratio of L acid content (i.e., the ratio of L acid) to the total of L acid content and B acid content), NH3-TPD, BET nitrogen adsorption-desorption. The results are shown in Table I-1.
[0248] [Table 1]
[0249] JPEG0007787888000002.jpg234169
[0250] Test Example I-2 This test example illustrates a process for producing 1,6-hexanediamine by hydroamination of 1,6-hexanediol using a catalyst according to a first type of embodiment of the present application.
[0251] 100 mL of the resulting catalyst was measured and placed in a fixed-bed reactor. It was activated using hydrogen at 220°C for 2 hours, then cooled to 168°C, and the system pressure was increased to 9.5 MPa using hydrogen. Ammonia was then metered into the reaction system via a metering pump, preheated to 150°C, and sent to the top of the reactor. Heat-molten 1,6-hexanediol was then fed to the top of the reactor via a metering pump, and hydrogen was steadily introduced via a gas mass flow meter. The molar ratio of hydrogen to ammonia to 1,6-hexanediol was 3:12:1, and the liquid-phase volumetric space velocity of 1,6-hexanediol was 0.45 h . -1 The catalytic amination reaction was carried out in a reactor at a reaction temperature of 198°C and a reaction pressure of 9.5 MPa. The reaction solution was sampled and analyzed after 200 hours of reaction time. The analytical results are shown in Table I-2.
[0252] Sample analysis was performed by gas chromatography and calibrated using the correction factors of formulated standards.
[0253] Conversion and selectivity were calculated based on the molar content of each component in the reaction solution.
[0254]
number
[0255] The selectivity for hexamethyleneimine was calculated by changing the numerator in the above formula for calculating the selectivity for hexanediamine to the molar content of hexamethyleneimine, the selectivity for aminohexanol was calculated by changing the numerator in the above formula for calculating the selectivity for hexanediamine to the molar content of aminohexanol, etc., and the selectivity for "other" was calculated by changing the numerator in the above formula for calculating the selectivity for hexanediamine to twice the molar content of the amine dimer, which refers to the dimer of 1,6-hexanediamine (i.e., bis(hexamethylene)triamine, also known as N-(6-aminohexyl)-1,6-hexanediamine), and the dimer of 1,6-hexanediamine and hexamethyleneimine (i.e., N-(6-aminohexyl)hexamethyleneimine)).
[0256] [Table 2]
[0257] As can be seen from the data in Table I-2, the catalysts of the present invention have higher conversions and higher activities than the comparative catalysts, indicating that the catalysts of the present invention provide faster reaction rates.
[0258] Test Example I-3 This test example illustrates a process for producing 1,3-propanediamine by hydroamination of 1,3-propanediol using a catalyst according to a first type of embodiment of the present application.
[0259] 100 mL of catalyst CI-3 obtained in Example I-3 was measured and placed in a fixed-bed reactor. It was activated using hydrogen at 220°C for 2 hours, then cooled to 165°C, and the system pressure was increased to 8.8 MPa using hydrogen. Ammonia was then metered into the reaction system via a metering pump, preheated to 120°C, and sent to the top of the reactor. 1,3-propanediol was fed to the top of the reactor via a metering pump, and hydrogen was steadily introduced via a gas mass flow meter. The molar ratio of hydrogen to ammonia to 1,3-propanediol was 3:9:1, and the liquid phase volumetric space velocity of 1,3-propanediol was 0.4 h / s . -1 The catalytic amination reaction was carried out in the reactor, and after the reaction stabilized, the reaction solution was sampled and analyzed (the analytical conditions and the calculation methods of conversion and selectivity were the same as those in Test Example I-2). The analytical results are shown in Table I-3.
[0260] [Table 3]
[0261] Test Example I-4 This test example illustrates a process for producing ethylamine by hydroamination of ethanol using a catalyst according to the first type of embodiment of the present application.
[0262] 100 mL of catalyst CI-3 obtained in Example I-3 was measured and placed in a fixed-bed reactor. It was activated using hydrogen at 220°C for 2 hours, then cooled to 170°C, and the system pressure was increased to 1.8 MPa using hydrogen. Ammonia was then metered into the reaction system via a metering pump, preheated to 125°C, and sent to the top of the reactor. Ethanol was then fed to the top of the reactor via a metering pump, and hydrogen was steadily introduced via a gas mass flow meter. The molar ratio of hydrogen, ammonia, and ethanol was 3:5:1, and the liquid phase volumetric space velocity of ethanol was 0.6 h / s . -1The catalytic amination reaction was carried out in a reactor at a reaction temperature of 180°C and a reaction pressure of 1.8 MPa. After the reaction stabilized, the reaction solution was sampled and analyzed (the analytical conditions and the calculation methods for conversion and selectivity were the same as those in Test Example I-2). The analytical results are shown in Table I-4.
[0263] [Table 4]
[0264] Catalysts DI-1 and DI-2 were tested under the same process conditions. Analysis revealed that comparative catalysts DI-1 and DI-2 produced more "other" components, with selectivities of 0.8% and 1.2%, respectively. Furthermore, over a long-term evaluation period (200 hours), catalysts DI-1 and DI-2 showed relatively high deactivation rates. After 200 hours of evaluation, the carbon deposition on catalyst CI-3 was significantly greater than that on catalysts DI-1 and DI-2. While the specific surface area and pore volume of catalyst CI-3 showed no significant decrease (less than 2%), the specific surface area of catalysts DI-1 and DI-2 decreased by 7% and 9%, respectively, and the pore volume of catalysts DI-1 and DI-2 decreased by 9% and 10%, respectively, indicating that the pore channels were blocked by carbon deposition.
[0265] Example Series II The second type of embodiment of the present application will be further described in detail below with reference to examples in Example Series II. In the following examples in Example Series II, the pseudoboehmite powder has an (Al2O3) content of 70 wt% on a dry basis, and the silica sol was purchased from Qingdao Ocean Chemical Co., Ltd. under the trade name JN-40.
[0266] Example II-1 Pseudoboehmite powder (380m 2The desired support was obtained by kneading the cellulose sintered body (having a specific surface area of 1.09 mL / g and a pore volume of 1.09 mL / g) with a dilute aqueous acid solution containing 5% by volume of nitric acid and 3.5% by volume of phosphoric acid, extruding it into strips, drying it at 120°C for 10 hours, and calcining it at 850°C for 4 hours. The detailed parameters are shown in Table II-1.
[0267] 141.56 g of nickel nitrate hexahydrate (technical grade, with a purity of 98%) was dissolved in water to obtain 166 mL of solution, and the pH of the solution was adjusted to 4.3. The solution was twice supported on 100 g of the obtained alumina support by spray impregnation, and after each spray impregnation, it was dried at 120°C for 8 hours, then calcined at 400°C for 4 hours, and then reduced with hydrogen while gradually increasing the temperature at a rate of 20°C / hour, and finally reduced at 440°C for 3 hours to obtain catalyst C-II-1.
[0268] Example II-2 Pseudoboehmite powder (400m 2 The pseudoboehmite powder and silica sol were used in an amount such that the weight ratio of Al2O3 to SiO2 in the support was 4:1.
[0269] 176.38 g of cobalt nitrate hexahydrate (technical grade, 98% purity) was dissolved in water to obtain 160 mL of solution, and the pH of the solution was adjusted to 3.9. The solution was loaded onto 100 g of the obtained support by wet impregnation in two steps, and after each wet impregnation, it was dried at 120 ° C for 6 hours and calcined at 390 ° C for 4 hours, and then reduced with hydrogen while gradually increasing the temperature at a rate of 20 ° C / hour, and finally reduced at 460 ° C for 5 hours to obtain catalyst C-II-2.
[0270] Example II-3 Pseudoboehmite powder (395m 2The desired support was obtained by kneading the sintered ...
[0271] 75.59 g of cobalt nitrate hexahydrate (technical grade, 98% purity) and 27.36 g of 50 wt % manganese nitrate solution were dissolved in water to obtain 138 mL of solution, and the pH of the solution was adjusted to 4.4. The solution was supported twice on 100 g of the obtained support by spray impregnation, and after each spray impregnation, it was dried at 120 ° C for 2 hours, then calcined at 400 ° C for 4 hours, and then reduced with hydrogen while gradually increasing the temperature at a rate of 20 ° C / hour, and finally reduced at 400 ° C for 8 hours to obtain catalyst C-II-3.
[0272] Example II-4 Pseudoboehmite powder (395m 2 The resulting granules (having a specific surface area of 1.05 mL / g and a pore volume of 1.05 mL / g) were kneaded with a dilute aqueous acid solution containing 5% by volume of nitric acid and 3% by volume of boric acid, extruded into strips, dried at 120°C for 18 hours, and then calcined at 1010°C for 4.5 hours to obtain the desired carrier. The detailed parameters are shown in Table II-1.
[0273] 60.47 g of cobalt nitrate hexahydrate (technical grade, 98% purity), 50.56 g of nickel nitrate hexahydrate (technical grade, 98% purity), and 0.73 g of ammonium perrhenate (99% purity) were dissolved in water to obtain 120 mL of solution, and the pH of the solution was adjusted to 4.3. The solution was loaded twice onto 100 g of the obtained support by isovolumetric impregnation, and after each impregnation, it was dried at 120 ° C for 5 hours, then calcined at 390 ° C for 4 hours, and then reduced with hydrogen while gradually increasing the temperature at a rate of 20 ° C / hour, and finally reduced at 450 ° C for 6 hours to obtain catalyst C-II-4.
[0274] Example II-5 Pseudoboehmite powder (382m 2The desired support was obtained by kneading the sintered ...
[0275] 192.12 g of nickel nitrate hexahydrate (technical grade, with a purity of 98%) and 3.94 g of silver nitrate were dissolved in water to obtain 182 mL of a solution, and the pH of the solution was adjusted to 4.6. The solution was supported twice on 100 g of the obtained support by spray impregnation, and after each spray impregnation, it was dried at 120°C for 4 hours, then calcined at 400°C for 4 hours, and then reduced with hydrogen while gradually increasing the temperature at a rate of 20°C / hour, and finally reduced at 480°C for 3 hours to obtain catalyst C-II-5.
[0276] Example II-6 Pseudoboehmite powder (375m 2 The desired support (having a specific surface area of 1.19 mL / g and a pore volume of 1.19 mL / g) was kneaded with a dilute acid solution containing 5% by volume of nitric acid and 3.5% by volume of phosphoric acid, extruded into toothed spheres, dried at 120°C for 15 hours, and then calcined at 880°C for 5.5 hours. The detailed parameters are shown in Table II-1.
[0277] 100.79 g of cobalt nitrate hexahydrate (technical grade, 98% purity) and 14.56 g of zinc nitrate (analytical pure) were dissolved in water to obtain 154 mL of solution, and the pH of the solution was adjusted to 5.1. The solution was twice supported on 100 g of the obtained support by spray impregnation, and after each spray impregnation, it was dried at 120 ° C for 6 hours and then calcined at 400 ° C for 4 hours, and then reduced with hydrogen while gradually increasing the temperature at a rate of 20 ° C / hour, and finally reduced at 450 ° C for 3 hours to obtain catalyst C-II-6.
[0278] Example II-7 Pseudoboehmite powder (342m 2The desired support was obtained by kneading the sintered ...
[0279] 120.94 g of cobalt nitrate hexahydrate (technical grade, 98% purity) and 9.28 g of bismuth nitrate pentahydrate (analytical pure) were dissolved in water to obtain 102 mL of solution, and the pH of the solution was adjusted to 4.9. The solution was supported on 100 g of the obtained support by wet impregnation twice, and after each wet impregnation, it was dried at 120°C for 4 hours, then calcined at 400°C for 4 hours, and then reduced with hydrogen while gradually increasing the temperature at a rate of 20°C / hour, and finally reduced at 430°C for 4 hours to obtain catalyst C-II-7.
[0280] Example II-8 Pseudoboehmite powder (280m 2 The resulting granules (having a specific surface area of 0.89 mL / g and a pore volume of 0.89 mL / g) were kneaded with a dilute acid solution containing 5% by volume of nitric acid, 2% by volume of hydrofluoric acid, and 0.5% by weight of selenium nitrate, extruded into toothed spheres, dried at 120°C for 20 hours, and then calcined at 980°C for 12 hours to obtain the desired carrier. The detailed parameters are shown in Table II-1.
[0281] 202.23 g of nickel nitrate hexahydrate (technical grade, 98% purity) and 13.65 g of zinc nitrate hexahydrate (analytical pure) were dissolved in water to obtain 128 mL of solution, and the pH of the solution was adjusted to 3.7. The solution was twice supported on 100 g of the obtained support by spray impregnation, and after each spray impregnation, it was dried at 120 ° C for 10 hours, then calcined at 400 ° C for 4 hours, and then reduced with hydrogen while gradually increasing the temperature at a rate of 20 ° C / hour, and finally reduced at 410 ° C for 6 hours to obtain catalyst C-II-8.
[0282] Example II-9 Pseudoboehmite powder (380m 2The pseudoboehmite powder and silica sol were used in an amount such that the weight ratio of Al2O3 to SiO2 in the support was 9:1.
[0283] 75.59 g of cobalt nitrate hexahydrate (technical grade, 98% purity), 50.56 g of nickel nitrate hexahydrate (technical grade, 98% purity), and 29.31 g of 50 wt % manganese nitrate solution were dissolved in water to obtain 106 mL of solution, and the pH of the solution was adjusted to 4.0. The solution was supported twice on 100 g of the obtained alumina support by spray impregnation, and after each spray impregnation, it was dried at 120 ° C for 8 hours and then calcined at 400 ° C for 4 hours, and then reduced with hydrogen while gradually increasing the temperature at a rate of 20 ° C / hour, and finally reduced at 440 ° C for 5 hours to obtain catalyst C-II-9.
[0284] Example II-10 Pseudoboehmite powder (369m 2 The desired support was obtained by kneading the cellulose acylate (having a specific surface area of 1.15 mL / g and a pore volume of 1.15 mL / g) with a dilute acid solution containing 5% by volume of nitric acid and 3% by volume of sulfuric acid, extruding it into strips, drying it at 120°C for 15 hours, and calcining it at 1010°C for 6.5 hours. The detailed parameters are shown in Table II-1.
[0285] 35.39 g of nickel nitrate hexahydrate (technical grade, 98% purity) and 2.18 g of ammonium perrhenate (99% purity) were dissolved in water to obtain 164 mL of solution, and the pH of the solution was adjusted to 5.3. The solution was supported twice on 100 g of the obtained support by spray impregnation. After each spray impregnation, the support was dried at 120 ° C for 6 hours and calcined at 350 ° C for 4 hours, and then reduced with hydrogen while gradually increasing the temperature at a rate of 20 ° C / hour, and finally reduced at 420 ° C for 5 hours to obtain catalyst C-II-10.
[0286] Comparative Example II-1 Catalyst D-II-1 was prepared as described in Example II-3, except that no sulfuric acid was added during the preparation of the support and the pH of the impregnation solution was not adjusted (it has an inherent pH of about 7).
[0287] Comparative Example II-2 Catalyst D-II-2 was prepared as described in Example II-3, except that sulfuric acid was used to adjust the S content in the support to the amount shown in Table II-1, and the pH of the impregnation solution was not adjusted (it has an inherent pH of about 7).
[0288] Comparative Example II-3 The catalyst was prepared as described in Example II-3, except that sulfuric acid was used so that the S content in the support was the amount shown in Table II-1, the calcination temperature was 650°C, the calcination time was 4 hours, and the pH of the impregnation solution was not adjusted (it had an inherent pH of about 7), to obtain Catalyst D-II-3.
[0289] Test Example II-1 The elemental composition of the support and catalyst was analyzed by plasma emission spectroscopy, and the content of elements (ions) other than the support was expressed as the content of the element per 100 g of matrix; the support obtained above was characterized by probe adsorption spectroscopy, NH3-TPD, BET nitrogen adsorption-desorption, and the particle size of the active metal component in the catalyst was measured by XRD. The results are shown in Table II-1.
[0290] [Table 5]
[0291] JPEG0007787888000008.jpg183169
[0292] Test Example II-2 This test example illustrates a process for producing 1,6-hexanediamine by hydroamination of 1,6-hexanediol using a catalyst according to a second type of embodiment of the present application.
[0293] 100 mL of the catalyst obtained in each example was measured and placed in a fixed-bed reactor. It was activated using hydrogen at 250°C for 4 hours, then cooled to 160°C, and the system pressure was increased to 11 MPa using hydrogen. Ammonia was then metered into the reaction system via a metering pump, preheated to 170°C, and then sent to the top of the reactor. Heat-molten 1,6-hexanediol was fed to the top of the reactor via a metering pump, and hydrogen was steadily introduced via a gas mass flow meter. The molar ratio of hydrogen to ammonia to 1,6-hexanediol was 4:10:1, and the liquid phase volumetric space velocity of 1,6-hexanediol was 0.4 h / s . -1 The catalytic amination reaction was carried out in the reactor at a reaction temperature of 185°C and a reaction pressure of 11 MPa, and the reaction solution was sampled and analyzed after 20 hours of reaction time. The analytical results are shown in Table II-2.
[0294] Sample analysis was performed by gas chromatography and calibrated using the correction factors of formulated standards.
[0295] The conversion and selectivity were calculated based on the molar content of each component in the reaction solution, and the calculation method was the same as that described in Test Example I-2.
[0296] [Table 6]
[0297] As can be seen from the data in Table II-2, the present catalysts have higher conversions and higher activities than the comparative catalysts, indicating that the present catalysts provide faster reaction rates.
[0298] Test Example II-3 This example illustrates a process for producing ethylenediamine by hydroamination of ethanolamine using a catalyst according to a second type of embodiment of the present application.
[0299] 100 mL of catalyst C-II-3 obtained in Example II-3 was measured and placed in a fixed-bed reactor. It was activated using hydrogen at 250°C for 2 hours, then cooled to 168°C, and the system pressure was increased to 8 MPa using hydrogen. Ammonia was then metered into the reaction system via a metering pump, preheated to 165°C, and sent to the top of the reactor. Ethanolamine was then fed to the top of the reactor via a metering pump, and hydrogen was steadily introduced via a gas mass flow meter. The molar ratio of hydrogen, ammonia, and ethanolamine was 3:10:1, and the liquid phase volumetric space velocity of ethanolamine was 0.75 h / min. -1 The catalytic amination was carried out in a reactor at a reaction temperature of 205°C and a reaction pressure of 8 MPa. After the reaction stabilized, the reaction solution was sampled and analyzed (the analytical conditions and the calculation methods for conversion and selectivity were the same as those in Test Example II-2). The analytical results are shown in Table II-3.
[0300] [Table 7]
[0301] Catalysts D-II-1 to D-II-4 were tested under the same process conditions, and the analytical results showed that comparative catalysts D-II-1 to D-II-4 produced more "other" components, and that catalysts D-II-1 to D-II-4 had lower selectivity and conversion and relatively high deactivation rates over long-term evaluation. After 500 hours of evaluation, the carbon deposition on catalyst C-II-3 was different from that on catalysts D-II-1 to D-II-4. The carbon deposition on the latter catalyst was significantly greater than that on catalyst C-II-3. While the decrease in the specific surface area and pore volume of catalyst C-II-3 was not obvious (less than 2%), the decrease in the specific surface area of catalysts D-II-1 to D-II-4 was 19%, 16%, 18%, and 16%, respectively, and the decrease in pore volume of catalysts D-II-1 to D-II-4 was 20%, 18%, 19%, and 18%, respectively, indicating that the carbon deposition on these catalysts was relatively large and caused blockage of the pore channels.
[0302] Example Series III The third type of embodiment of the present application will be described in more detail with reference to the examples in Example Series III. In the following examples in Example Series III, the pseudoboehmite powder used has an (AlO) content of 72 wt % on a dry basis; the silica sol was purchased from Qingdao Ocean Chemical Co., Ltd. under the trade name JN-40.
[0303] Example III-1 Pseudoboehmite powder (315m) prepared by the aluminum sulfate method 2 / g specific surface area and 0.96 mL / g pore volume, and the P element content in the powder was 3.6 g per 100 g of alumina) was kneaded with a dilute acid aqueous solution containing 5 vol % nitric acid, extruded into several elongated pieces with a diameter of 5 mm, cut into lengths of 4 mm, dried at 120°C for 8 hours, and calcined at 760°C for 5 hours to obtain a support.
[0304] 186.5 g of cobalt nitrate hexahydrate (technical grade, 98% purity) was dissolved in water to obtain 142 mL of solution. The cobalt nitrate solution was twice supported on 100 g of the obtained support by spray impregnation. After each spray impregnation, the support was dried at 120°C for 4 hours, then calcined at 400°C for 4 hours, and then reduced with hydrogen while gradually increasing the temperature at a rate of 20°C / hour, and finally reduced at 430°C for 3 hours to obtain catalyst C-III-1.
[0305] Example III-2 Pseudoboehmite powder (295m) prepared by the aluminum sulfate method 2 / g specific surface area and 0.93 mL / g pore volume, and the B element content in the powder was 0.8 g per 100 g of alumina) was kneaded and mixed uniformly with a dilute acid aqueous solution containing 5 vol% nitric acid, extruded into clover-shaped granules with a thickness of 3 mm, dried at 100°C for 15 hours, and calcined at 930°C for 4 hours to obtain a support.
[0306] 151.7 g of nickel nitrate hexahydrate (technical grade, 98% purity) was dissolved in water to obtain 158 mL of solution, which was then spray-impregnated twice onto 100 g of the obtained support, dried at 100°C for 8 hours after each spray impregnation, calcined at 390°C for 4 hours, and then reduced with hydrogen at a gradual temperature increase rate of 20°C / hour, and finally reduced at 440°C for 3 hours to obtain catalyst C-III-2.
[0307] Example III-3 Pseudoboehmite powder (278m) prepared by the aluminum sulfate method 2 / g specific surface area and 0.85 mL / g pore volume, with the sulfur element content in the powder being 0.4 g per 100 g of alumina) was kneaded with a dilute acid aqueous solution containing 3.5 vol% nitric acid, and silica sol was added during the kneading process to mix uniformly. The silica sol was extruded into toothed spheres with a diameter of 4 mm, dried at 150°C for 6 hours, and calcined at 980°C for 3 hours to obtain a support. The amount of silica sol used was adjusted so that the mass ratio of silica to alumina in the support was 4:1.
[0308] 68.92 g of cobalt nitrate hexahydrate (technical grade, 98% purity) was dissolved in water to obtain 112 mL of solution, which was then spray-impregnated twice onto 100 g of the resulting alumina support, dried at 110°C for 8 hours after each spray impregnation, calcined at 390°C for 4 hours, reduced with hydrogen at a rate of gradually increasing the temperature at 20°C / hour, and finally reduced at 460°C for 2 hours to obtain catalyst C-III-3.
[0309] Example III-4 Pseudoboehmite powder (325m) prepared by the aluminum sulfate method 2The desired support was obtained by homogeneously mixing alumina (ZSM-5, Catalyst Factory, Nankai University, SiO2 / Al2O3 = 45 (molar ratio)) with a specific surface area of 0.1 / g, a pore volume of 1.12 mL / g, and an F content of 2.2 g per 100 g of alumina. The mixture was then kneaded with a dilute acid solution containing 5% by volume of nitric acid. The mixture was extruded into strips with a diameter of 5 mm, cut into 4 mm lengths, dried at 80°C for 20 hours, and calcined at 730°C for 8 hours. The amount of ZSM-5 molecular sieve powder was adjusted so that the content of pseudoboehmite-derived alumina in the support accounted for 90% of the total support mass.
[0310] 126 g of cobalt nitrate hexahydrate (technical grade, 98% purity) was dissolved in water to obtain 202 mL of solution. The cobalt nitrate solution was twice supported on 100 g of the obtained alumina support by spray impregnation. After each spray impregnation, the support was dried at 90°C for 20 hours, then calcined at 400°C for 4 hours, and then reduced with hydrogen while gradually increasing the temperature at a rate of 20°C / hour, and finally reduced at 430°C for 3 hours to obtain catalyst C-III-4.
[0311] Example III-5 Pseudoboehmite powder (260m) prepared by the aluminum sulfate method 2 The pseudoboehmite powder (having a specific surface area of 0.25 / g, a pore volume of 0.82 mL / g, and a P content of 0.6 g per 100 g of alumina) was kneaded with a dilute acid solution containing nitric acid and boric acid, extruded into cloverleaf-shaped granules 3 mm thick, dried at 100°C for 8 hours, and then calcined at 1005°C for 3 hours to obtain the desired support. The amount of boric acid used, calculated as Al2O3, was 2.29 g per 100 g of pseudoboehmite powder used, and the nitric acid concentration of the dilute acid solution was 5% by volume.
[0312] 75.6 g of cobalt nitrate hexahydrate (technical grade, 98% purity) was dissolved in water to obtain 122 mL of solution. The cobalt nitrate solution was twice supported on 100 g of the obtained support by spray impregnation. After each spray impregnation, the support was dried at 120°C for 4 hours, calcined at 390°C for 4 hours, and then reduced with hydrogen while gradually increasing the temperature at a rate of 20°C / hour, and finally reduced at 440°C for 3 hours to obtain catalyst C-III-5.
[0313] Example III-6 Pseudoboehmite powder (345m) prepared by the aluminum sulfate method 2 The pseudoboehmite powder (having a specific surface area of 0.02 g / g, a pore volume of 1.09 mL / g, and a B element content of 0.02 g per 100 g of alumina) was kneaded with a dilute acid solution containing nitric acid and sulfuric acid, extruded into toothed spheres with a diameter of 4 mm, dried at 120°C for 10 hours, and calcined at 750°C for 12 hours to obtain the desired support. The amount of sulfuric acid used, calculated as Al2O3, was 0.24 g per 100 g of pseudoboehmite powder used, and the nitric acid concentration in the dilute acid solution was 5% by volume.
[0314] 126.4 g of nickel nitrate hexahydrate (technical grade, 98% purity) was dissolved in water to obtain 184 mL of solution. The nickel nitrate solution was twice supported on 100 g of the obtained support by spray impregnation. After each spray impregnation, the support was dried at 120°C for 4 hours, calcined at 400°C for 4 hours, and then reduced with hydrogen while gradually increasing the temperature at a rate of 20°C / hour, and finally reduced at 430°C for 3 hours to obtain catalyst C-III-6.
[0315] Example III-7 Pseudoboehmite powder (320m) prepared by the aluminum sulfate method 2The pseudoboehmite powder (having a specific surface area of 0.1 g / g, a pore volume of 0.93 mL / g, and an S element content of 0.1 g per 100 g of alumina) was kneaded with a dilute acid solution containing nitric acid and phosphoric acid, extruded into toothed spheres with a diameter of 4 mm, dried at 100°C for 15 hours, and calcined at 780°C for 10 hours to obtain the desired support. The amount of phosphoric acid used, calculated as Al2O3, was 6.01 g per 100 g of pseudoboehmite powder used. The concentration of nitric acid in the dilute acid solution was 5% by volume.
[0316] 296.85 g of cobalt nitrate hexahydrate (technical grade, 98% purity) was dissolved in water to obtain 138 mL of solution. The cobalt nitrate solution was twice supported on 100 g of the obtained alumina support by spray impregnation. After each spray impregnation, the support was dried at 120°C for 5 hours, then calcined at 400°C for 4 hours, and then reduced with hydrogen while gradually increasing the temperature at a rate of 20°C / hour, and finally reduced at 450°C for 3 hours to obtain catalyst C-III-7.
[0317] Example III-8 Pseudoboehmite powder (295m) prepared by the aluminum sulfate method 2 / g specific surface area and pore volume of 0.88 mL / g, and the content of S element in the powder is 0.2 g per 100 g of alumina) was kneaded with a dilute acid aqueous solution containing 5 vol% nitric acid, extruded into toothed spheres with a diameter of 4 mm, dried at 90 °C for 18 hours, and calcined at 810 °C for 8 hours to obtain the desired carrier.
[0318] 100.8 g of cobalt nitrate hexahydrate (technical grade, 98% purity) was dissolved in water to obtain 134 mL of solution, which was then spray-impregnated twice onto 100 g of the obtained support, which was then dried at 100°C for 8 hours after each spray impregnation, calcined at 400°C for 4 hours, and then reduced with hydrogen at a temperature gradually increasing at a rate of 20°C / hour, and finally reduced at 420°C for 3 hours to obtain catalyst C-III-8.
[0319] Example III-9 Pseudoboehmite powder (340m) prepared by the aluminum sulfate method 2The powder (having a specific surface area of 0.12 g / g, a pore volume of 1.18 mL / g, and an F element content of 0.12 g per 100 g of alumina) was kneaded with a dilute acid solution containing 5% by volume of nitric acid, and silica sol was added during the kneading process. The resulting material was extruded into a cylindrical rod with a diameter of 3 mm, dried at 100°C for 16 hours, and calcined at 850°C for 6 hours to obtain the desired support. The amount of silica sol used was adjusted so that the molar ratio of silica to alumina in the support was 73:27.
[0320] 176.4 g of cobalt nitrate hexahydrate (technical grade, 98% purity) and 1.3 g of silver nitrate (analytical purity) were dissolved in water to obtain 178 mL of solution. The solution was twice supported on 100 g of the above-obtained support by spray impregnation, and after each spray impregnation, it was dried at 120 ° C for 4 hours, then calcined at 360 ° C for 4 hours, and then reduced with hydrogen while gradually increasing the temperature at a rate of 20 ° C / hour, and finally reduced at 450 ° C for 3 hours to obtain catalyst C-III-9.
[0321] Example III-10 Pseudoboehmite powder (310m) prepared by the aluminum sulfate method 2 / g specific surface area and 0.92 mL / g pore volume, with the sulfur element content in the powder being 1.4 g per 100 g of alumina) was kneaded with a dilute acid aqueous solution containing 5 vol% nitric acid, extruded into strips with a diameter of 5 mm, dried at 100°C for 12 hours, and calcined at 760°C for 10 hours to obtain the desired support.
[0322] 126g of cobalt nitrate hexahydrate (technical grade, 98% purity) and 13.7g of zinc nitrate hexahydrate (analytical purity) were dissolved in water to obtain 172mL of solution.This solution was twice supported on 100g of the above-obtained support by spray impregnation, and after each spray impregnation, it was dried at 120°C for 4 hours, then calcined at 400°C for 4 hours, and then reduced with hydrogen while gradually increasing the temperature at a rate of 20°C / hour, and finally reduced at 420°C for 3 hours to obtain catalyst C-III-10.
[0323] Example III-11 Pseudoboehmite powder (305m) prepared by the aluminum sulfate method 2 / g specific surface area and 0.94 mL / g pore volume, and the P element content in the powder was 1.55 g per 100 g of alumina) was kneaded with a dilute acid aqueous solution containing 5 vol% nitric acid, extruded into multiple strips with a diameter of 5 mm, dried at 120°C for 6 hours, and calcined at 860°C for 5 hours to obtain the desired support.
[0324] 141.1g of cobalt nitrate hexahydrate (technical grade, 98% purity) and 19.5g of 50% manganese nitrate aqueous solution were dissolved in water to obtain 168mL of solution.This solution was supported twice on 100g of the above-obtained support by spray impregnation, and after each spray impregnation, it was dried at 120°C for 4 hours, then calcined at 400°C for 4 hours, and then reduced with hydrogen while gradually increasing the temperature at a rate of 20°C / hour, and finally reduced at 420°C for 3 hours to obtain catalyst C-III-11.
[0325] Comparative example III-1 Catalyst D-III-1 was prepared as described in Example III-8, except that pseudo-boehmite powders with different S element contents were used, as shown in Table III-1, and the calcination temperature and calcination time in the preparation of the carrier were 700°C and 4 hours, respectively.
[0326] Comparative example III-2 Pseudoboehmite powder (224m) containing no doping elements 2 Catalyst D-III-2 was prepared as described in Example III-8, except that a zeolite (having a specific surface area of 0.95 mL / g and a pore volume of 0.95 mL / g) was used.
[0327] Comparative example III-3 Catalyst D-III-3 was prepared as described in Example III-8, except that pseudo-boehmite powders with different S element contents were used, the S element contents being as shown in Table III-1, and the calcination temperature and calcination time in the preparation of the carrier were 500°C and 4 hours, respectively.
[0328] Test Example III-1 The elemental compositions of the supports and catalysts were analyzed by plasma emission spectroscopy. The contents of doping elements, active metal components, and metal promoters were expressed by weight per 100 g of matrix. The obtained supports were characterized by probe adsorption spectroscopy and BET nitrogen adsorption-desorption. The results are shown in Table III-1.
[0329] [Table 8]
[0330] Test Example III-2 This test example illustrates a process for producing 1,6-hexanediamine by hydroamination of 1,6-hexanediol using a catalyst according to a third type of embodiment of the present application.
[0331] 100 mL of the catalyst obtained in each example was measured and placed in a fixed-bed reactor. It was activated using hydrogen at 220°C for 2 hours, then cooled to 170°C. The system pressure was increased to 10 MPa using hydrogen, and ammonia was metered into the reaction system via a metering pump, preheated to 150°C, and then sent to the top of the reactor. Heat-melted 1,6-hexanediol was fed to the top of the reactor via a metering pump, and hydrogen was steadily introduced via a gas mass flow meter. The molar ratio of hydrogen to ammonia to 1,6-hexanediol was 3:10:1, and the liquid phase volumetric space velocity of 1,6-hexanediol was 0.45 h / min. -1 The catalytic amination reaction was carried out in a reactor at a reaction temperature of 190°C and a reaction pressure of 10 MPa. The reaction solution was sampled and analyzed after 240 hours of reaction time. The analytical results are shown in Table III-2.
[0332] Sample analysis was performed by gas chromatography and calibrated using the correction factors of formulated standards.
[0333] The conversion and selectivity were calculated based on the molar content of each component in the reaction solution, and the calculation method was the same as that described in Test Example I-2.
[0334] [Table 9]
[0335] The "Other" in the table refers to amines containing 12 carbon atoms, which are difficult to dissipate from the pore channels due to the relative amount of amines produced, causing blocking of the pore channels and subsequently increasing the amount of carbon deposition, resulting in a rapid decline in catalyst activity. After 240 hours of evaluation, the catalysts were discharged and subjected to thermogravimetric analysis. The results show that the carbon deposition of catalysts D-III-1, D-III-2, and D-III-3 was at least twice that of catalysts C-III-1 to C-III-11.
[0336] After 1000 hours of evaluation, the results show that there is no obvious decrease in the catalytic activity of catalysts C-III-1 to C-III-11. That is, the conversion and selectivity of the catalysts determined after 1000 hours of continuous use are not substantially reduced compared to the conversion and selectivity of the catalysts determined after 240 hours of use. The conversions of catalysts D-III-1, D-III-2, and D-III-3 decrease by 29%, 32%, and 35%, respectively, and the selectivities to hexanediamine of these catalysts decrease by 15.1%, 12.8%, and 16.3%, respectively.
[0337] Test Example III-3 This test example illustrates a process for producing ethylamine by hydroamination of ethanol using a catalyst according to a third type of embodiment of the present application.
[0338] 100 mL of catalyst C-III-8 obtained in Example III-8 was measured and placed in a fixed-bed reactor. It was activated with hydrogen at 220°C for 2 hours, then cooled to 160°C, and the system pressure was increased to 1.6 MPa with hydrogen. Ammonia was then metered into the reaction system via a metering pump, preheated to 135°C, and then sent to the top of the reactor. Ethanol was also fed to the top of the reactor via a metering pump, and hydrogen was steadily introduced via a gas mass flow meter. The molar ratio of hydrogen, ammonia, and ethanol was 3:8:1, and the liquid phase volumetric space velocity of ethanol was 0.45 h / min. -1 The catalytic amination reaction was carried out in a reactor at a reaction temperature of 170°C and a reaction pressure of 1.6 MPa. After the reaction stabilized, the reaction solution was sampled and analyzed (the analytical conditions and the calculation methods for conversion and selectivity were the same as those in Test Example III-2). The analytical results are shown in Table III-3.
[0339] [Table 10]
[0340] Test Example III-4 This test example illustrates a process for producing isopropylamine by hydroamination of acetone using a catalyst according to a third type of embodiment of the present application.
[0341] 100 mL of catalyst C-III-10 obtained in Example III-10 was measured and placed in a fixed-bed reactor. It was activated with hydrogen at 200°C for 2 hours, then cooled to 145°C, and the system pressure was increased to 1.5 MPa with hydrogen. Ammonia was then metered into the reaction system via a metering pump, preheated to 110°C, and sent to the top of the reactor. Acetone was then fed to the top of the reactor via a metering pump, and hydrogen was steadily introduced via a gas mass flow meter. The molar ratio of hydrogen, ammonia, and acetone was 3:6:1, and the liquid phase volumetric space velocity of acetone was 0.4 h / s . -1The catalytic amination reaction was carried out in a reactor, and after the reaction stabilized, the reaction solution was sampled and analyzed (the analytical conditions and the calculation methods for conversion and selectivity were the same as those in Test Example III-2). The analytical results are shown in Table III-4.
[0342] [Table 11]
[0343] Example Series IV The fourth type of embodiment of the present application will be described in further detail below with reference to examples in Example Series IV. In the following examples in Example Series IV, the pseudoboehmite powder has an (Al2O3) content of 70 wt% on a dry basis; the silica sol was purchased from Qingdao Ocean Chemical Co., Ltd. under the trade name JN-40.
[0344] Example IV-1 Pseudoboehmite powder (288m) prepared by the aluminum sulfate method 2 Pseudo-boehmite powder (having a specific surface area of 0.22 g / g and a pore volume of 0.91 mL / g, and the doping element P present in the pseudo-boehmite powder was calculated as Al2O3, and the amount was 0.22 g per 100 g of pseudo-boehmite powder used, calculated as Al2O3) was kneaded with a dilute acid solution containing 5% by volume of nitric acid, extruded into strips with a diameter of 5 mm, cut into 4 mm lengths, dried at 120 °C for 8 hours, and calcined at 550 °C for 6 hours. 32.1 g of magnesium nitrate hexahydrate (analytically pure) was dissolved in water to obtain 85 mL of solution. This magnesium nitrate aqueous solution was spray-impregnated onto 100 g of the calcined product, dried at 100 °C for 10 hours, and then calcined at 820 °C for 5 hours to obtain the desired support.
[0345] 186.5g of cobalt nitrate hexahydrate (technical grade, 98% purity), 6.83g of zinc nitrate hexahydrate (analytical purity) and 1.16g of bismuth nitrate pentahydrate (analytical purity) were dissolved in water to obtain 148mL of solution. The solution was supported twice on the obtained support by spray impregnation, and after each spray impregnation, it was dried at 120°C for 4 hours, then calcined at 400°C for 4 hours, and then reduced with hydrogen while gradually increasing the temperature at a rate of 20°C / hour, and finally reduced at 430°C for 3 hours to obtain catalyst C-IV-1.
[0346] Example IV-2 Pseudoboehmite powder (285m) prepared by the aluminum sulfate method 2 The pseudo-boehmite powder (having a specific surface area of 0.25 / g and a pore volume of 0.93 mL / g, and the doping element B present in the pseudo-boehmite powder was calculated as Al2O3 and was 0.53 g per 100 g of the pseudo-boehmite powder used, calculated as Al2O3) was kneaded with a dilute acid solution containing 5 vol% nitric acid, extruded into cloverleaf-shaped granules with a thickness of 3 mm, dried at 120 °C for 15 hours, and calcined at 520 °C for 8 hours. 11.8 g of calcium nitrate tetrahydrate (analytical pure) was dissolved in water to obtain 91 mL of solution, which was then spray-impregnated onto 100 g of the calcined product, dried at 110 °C for 10 hours, and calcined at 800 °C for 6 hours to obtain the desired support.
[0347] 151.7 g of nickel nitrate hexahydrate (technical grade, 98% purity), 6.83 g of zinc nitrate hexahydrate (analytical pure) and 1.16 g of bismuth nitrate pentahydrate (analytical pure) were dissolved in water to obtain 156 mL of solution. The solution was supported twice on the obtained support by spray impregnation, and after each spray impregnation, it was dried at 120 ° C for 4 hours, then calcined at 400 ° C for 4 hours, and then reduced with hydrogen while gradually increasing the temperature at a rate of 20 ° C / hour, and finally reduced at 430 ° C for 3 hours to obtain catalyst C-IV-2.
[0348] Example IV-3 Pseudoboehmite (285m) was prepared by the aluminum sulfate method using a dilute acid solution containing 5% by volume of nitric acid.2 The pseudo-boehmite powder (having a specific surface area of 0.23 g / g and a pore volume of 0.9 mL / g, and the doping element P present in the pseudo-boehmite powder was calculated as Al2O3, and the amount was 0.23 g per 100 g of pseudo-boehmite powder used, calculated as Al2O3) was homogeneously mixed, extruded into strips with a diameter of 5 mm, cut into 4 mm lengths, dried at 120°C for 8 hours, and then calcined at 550°C for 6 hours. 32.1 g of magnesium nitrate hexahydrate (analytically pure) was dissolved in water to obtain 85 mL of solution. The magnesium nitrate aqueous solution was supported on 100 g of the calcined product by spray impregnation, dried at 100°C for 10 hours, and then calcined at 820°C for 5 hours to obtain the desired support.
[0349] 45.4g of cobalt nitrate hexahydrate (technical grade, 98% purity), 6.83g of zinc nitrate hexahydrate (analytical pure) and 1.16g of bismuth nitrate pentahydrate (analytical pure) were dissolved in water to obtain 146mL of solution. The solution was supported twice on the obtained support by spray impregnation, and after each spray impregnation, it was dried at 120°C for 4 hours, then calcined at 400°C for 4 hours, and then reduced with hydrogen while gradually increasing the temperature at a rate of 20°C / hour, and finally reduced at 430°C for 3 hours to obtain catalyst C-IV-3.
[0350] Example IV-4 The support was prepared as described in Example IV-1, except that the pseudoboehmite powder was uniformly mixed with molecular sieve powder (ZSM-5, Catalyst Factory, Nankai University, SiO2 / Al2O3 = 45 (molar ratio)), and the amount of ZSM-5 molecular sieve powder was adjusted so that the content of alumina derived from pseudoboehmite in the support accounted for 85% of the total mass of the support.
[0351] 176.4 g of cobalt nitrate hexahydrate (technical grade, 98% purity), 4.55 g of zinc nitrate hexahydrate (analytical purity) and 2.32 g of bismuth nitrate pentahydrate (analytical purity) were dissolved in water to obtain 178 mL of solution. The solution was supported twice on the obtained support by spray impregnation, and after each spray impregnation, it was dried at 120 ° C for 4 hours, then calcined at 400 ° C for 4 hours, and then reduced with hydrogen while gradually increasing the temperature at a rate of 20 ° C / hour, and finally reduced at 430 ° C for 3 hours to obtain catalyst C-IV-4.
[0352] Example IV-5 Pseudoboehmite powder (258m) prepared by the aluminum sulfate method 2 Pseudoboehmite powder (having a specific surface area of 0.18 g / g and a pore volume of 0.65 mL / g, with the doping element P present in the powder calculated as Al2O3 in an amount of 0.18 g per 100 g of pseudoboehmite powder used) was kneaded with a dilute aqueous acid solution containing 4.5 vol% nitric acid, extruded into cloverleaf-shaped granules with a thickness of 4 mm, dried at 100 °C for 18 hours, and then calcined at 560 °C for 5 hours. 11.8 g of calcium nitrate tetrahydrate (analytical pure) was dissolved in water to obtain 73 mL of solution. The calcium nitrate aqueous solution was spray-impregnated onto 100 g of the calcined product, which was then dried at 120 °C for 10 hours and further calcined at 970 °C for 6 hours to obtain the desired support.
[0353] 75.6g of cobalt nitrate hexahydrate (technical grade, 98% purity), 4.55g of zinc nitrate hexahydrate (analytical purity) and 2.32g of bismuth nitrate pentahydrate (analytical purity) were dissolved in water to obtain 124mL of solution. The solution was supported twice on the obtained support by spray impregnation. After each spray impregnation, it was dried at 100°C for 10 hours, then calcined at 388°C for 4 hours, and then reduced with hydrogen while gradually increasing the temperature at a rate of 20°C / hour, and finally reduced at 420°C for 4 hours to obtain catalyst C-IV-5.
[0354] Example IV-6 Pseudoboehmite (318m) prepared by the aluminum sulfate method 2Pseudoboehmite powder (having a specific surface area of 0.25 / g and a pore volume of 0.93 mL / g, with the doping element B present in the powder (calculated as Al2O3, 3.66 g per 100 g of pseudoboehmite powder used) was kneaded with a dilute acid solution containing 5% by volume nitric acid. Silica sol (JN-40, available from Qingdao Ocean Chemical Co., Ltd.) was added during the kneading process, and the mixture was homogeneously mixed. The mixture was extruded into 3.5 mm diameter toothed spheres, dried at 120°C for 4 hours, and then calcined at 630°C for 5 hours. 7.6 g of barium nitrate (analytical pure) was dissolved in water to obtain 88 mL of solution. The barium nitrate aqueous solution was spray-impregnated onto 100 g of the calcined product, which was then dried at 100°C for 12 hours and calcined at 880°C for 3 hours to obtain the desired support. The amount of silica sol used was adjusted so that the mass ratio of alumina to silica in the carrier was 4:1.
[0355] 126.4g of nickel nitrate hexahydrate (technical grade, 98% purity), 4.55g of zinc nitrate hexahydrate (analytical purity) and 2.32g of bismuth nitrate pentahydrate (analytical purity) were dissolved in water to obtain 160mL of solution. This solution was spray-loaded twice onto the obtained support, and after each spray impregnation, it was dried at 120°C for 4 hours, then calcined at 400°C for 4 hours, and then reduced with hydrogen while gradually increasing the temperature at a rate of 20°C / hour, and finally reduced at 420°C for 3.5 hours to obtain catalyst C-IV-6.
[0356] Example IV-7 The carrier obtained in Example IV-1 was used.
[0357] 201.6 g of cobalt nitrate hexahydrate (technical grade, 98% purity), 6.83 g of zinc nitrate hexahydrate (analytical purity), and 1.16 g of bismuth nitrate pentahydrate (analytical purity) were dissolved in water to obtain 150 mL of solution. The solution was supported twice on the obtained support by spray impregnation, and after each spray impregnation, it was dried at 120 ° C for 4 hours, then calcined at 400 ° C for 4 hours, and then reduced with hydrogen while gradually increasing the temperature at a rate of 20 ° C / hour, and finally reduced at 430 ° C for 3 hours to obtain catalyst C-IV-7.
[0358] Example IV-8 Pseudoboehmite (290m) prepared by the aluminum sulfate method 2 Pseudoboehmite powder (with a specific surface area of 0.88 g / g and a pore volume of 0.78 mL / g, calculated as Al2O3, and containing 0.88 g of doping element S per 100 g of pseudoboehmite powder) was kneaded with a dilute acid solution containing 4.5% by volume of nitric acid. Silica sol was added during the kneading process, mixed uniformly, and extruded into clover-shaped granules with a thickness of 4 mm. These were dried at 80°C for 20 hours and then calcined at 550°C for 7 hours. 17.7 g of calcium nitrate tetrahydrate (analytical pure) was dissolved in water to obtain 84 mL of solution. The calcium nitrate aqueous solution was spray-impregnated onto 100 g of the calcined product, which was then dried at 120°C for 10 hours and calcined at 900°C for 4 hours to obtain the desired support. The amount of silica sol used was adjusted so that the molar ratio of silica to alumina in the support was 86:14.
[0359] 100.8g of cobalt nitrate hexahydrate (technical grade, 98% purity), 2.88g of zinc nitrate hexahydrate (analytical purity) and 3.48g of bismuth nitrate pentahydrate (analytical purity) were dissolved in water to obtain 152mL of solution. The solution was supported twice on the obtained support by spray impregnation, and after each spray impregnation, it was dried at 100°C for 10 hours, then calcined at 400°C for 4 hours, and then reduced with hydrogen while gradually increasing the temperature at a rate of 20°C / hour, and then reduced at 430°C for 4 hours to obtain catalyst C-IV-8.
[0360] Example IV-9 Pseudoboehmite (320m) prepared by the aluminum sulfate method 2 Pseudo-boehmite powder (having a specific surface area of 0.1 / g and a pore volume of 0.95 mL / g, with the doping element F present in the powder calculated as Al2O3 (0.82 g per 100 g of pseudo-boehmite powder used) was kneaded with a dilute acid solution containing 5.2 vol% nitric acid. Silica sol was added during the kneading process, uniformly mixed, and extruded into clover-shaped granules with a thickness of 3 mm. The granules were dried at 100 °C for 8 hours and then calcined at 620 °C for 4 hours. 3.8 g of barium nitrate (analytical pure) was dissolved in water to obtain 83 mL of solution. The barium nitrate aqueous solution was spray-impregnated onto 100 g of the calcined product, which was then dried at 120 °C for 8 hours and calcined at 950 °C for 5 hours to obtain the desired support. The amount of silica sol used was adjusted so that the molar ratio of silica to alumina in the support was 89:11.
[0361] 176.4 g of cobalt nitrate hexahydrate (technical grade, 98% purity), 2.88 g of zinc nitrate hexahydrate (analytical purity) and 3.48 g of bismuth nitrate pentahydrate (analytical purity) were dissolved in water to obtain 160 mL of solution. The solution was supported twice on the obtained support by spray impregnation, and after each spray impregnation, it was dried at 110 ° C for 8 hours, then calcined at 400 ° C for 4 hours, and then reduced with hydrogen while gradually increasing the temperature at a rate of 20 ° C / hour, and finally reduced at 420 ° C for 4.5 hours to obtain catalyst C-IV-9.
[0362] Example IV-10 Pseudoboehmite powder (291m) prepared by the aluminum sulfate method 2Pseudo-boehmite powder (having a specific surface area of 0.95 g / g and a pore volume of 0.93 mL / g, where the doping element S present in the powder was calculated as Al2O3 and was present in an amount of 0.95 g per 100 g of pseudo-boehmite powder used) was kneaded with a dilute acid solution containing 4 vol% nitric acid, extruded into cloverleaf-shaped granules with a thickness of 3.5 mm, dried at 100 °C for 8 hours, and then calcined at 600 °C for 5 hours. 42.7 g of magnesium nitrate hexahydrate (analytically pure) was dissolved in 92 mL of water, and the magnesium nitrate aqueous solution was spray-impregnated onto 100 g of the calcined product, dried at 120 °C for 8 hours, and further calcined at 830 °C for 8 hours to obtain the desired support.
[0363] 226.8g of cobalt nitrate hexahydrate (technical grade, 98% purity), 2.88g of zinc nitrate hexahydrate (analytical pure) and 4.64g of bismuth nitrate pentahydrate (analytical pure) were dissolved in water to obtain 172mL of solution. The solution was supported twice on the obtained support by spray impregnation. After each spray impregnation, it was dried at 120°C for 6 hours, then calcined at 400°C for 4 hours, and then reduced with hydrogen while gradually increasing the temperature at a rate of 20°C / hour, and finally reduced at 420°C for 4.5 hours to obtain catalyst C-IV-10.
[0364] Example IV-11 Catalyst C-IV-11 was prepared as described in Example IV-1, except that the pseudo-boehmite powder used was doped with element P, and element P was present in the pseudo-boehmite powder in an amount of 4.3 g, calculated as AlO, per 100 g of pseudo-boehmite powder used.
[0365] Example IV-12 The pseudo-boehmite powder used did not contain any doping elements and had a viscosity of 286 m 2 Catalyst C-IV-12 was prepared as described in Example IV-2, except that it had a specific surface area of 0.93 mL / g and a pore volume of 0.93 mL / g.
[0366] Example IV-13 Catalyst C-IV-13 was prepared as described in Example IV-2, except that the second calcination temperature was 1200°C.
[0367] Comparative example IV-1 Catalyst D-IV-1 was prepared as described in Example IV-5, except that the solution used for spray impregnation of the support was prepared by replacing the aqueous calcium nitrate solution with an equal volume of water and dissolving 151.7 g of nickel nitrate hexahydrate (technical grade, 98% purity) in water to obtain 158 mL of solution, so that only nickel was supported on the catalyst as the active metal component.
[0368] Comparative example IV-2 Catalyst D-IV-2 was prepared as described in Example IV-3, except that the solution used for spray impregnation of the support was prepared by dissolving 45.4 g of cobalt nitrate hexahydrate (technical grade, with a purity of 98%) and 1.16 g of bismuth nitrate pentahydrate (analytically pure) in water to obtain 148 mL of solution.
[0369] Comparative example IV-3 Catalyst D-IV-3 was prepared as described in Example IV-1, except that zinc nitrate was replaced with 8.5 g of copper nitrate trihydrate.
[0370] Test Example IV-1 The elemental composition of the support and catalyst was analyzed by plasma emission spectroscopy, and the content of elements (ions) other than the support was expressed by weight relative to 100 g of matrix; the obtained support was characterized by probe adsorption spectroscopy, BET nitrogen adsorption-desorption. The results are shown in Table IV-1.
[0371] [Table 12]
[0372] Test Example IV-2 This test example illustrates a process for producing 1,6-hexanediamine by hydroamination of 1,6-hexanediol using a catalyst according to a fourth type of embodiment of the present application.
[0373] 100 mL of the catalyst obtained in each of the examples and comparative examples was measured and placed in a fixed-bed reactor. It was activated using hydrogen at 220°C for 2 hours, then cooled to 172°C, and the pressure of the system was increased to 12.5 MPa using hydrogen. Next, ammonia was metered into the reaction system via a metering pump, preheated to 150°C, and sent to the top of the reactor. Then, heated and melted 1,6-hexanediol was fed to the top of the reactor via a metering pump, and hydrogen was steadily introduced via a gas mass flow meter. The molar ratio of hydrogen, ammonia, and 1,6-hexanediol was 3:18:1, and the liquid phase volumetric space velocity of 1,6-hexanediol was 0.5 h / min. -1 The catalytic amination reaction was carried out in a reactor at a reaction temperature of 195°C and a reaction pressure of 12.5 MPa. After the reaction stabilized, the reaction solution was sampled and analyzed. The analytical results are shown in Table IV-2.
[0374] Sample analysis was performed by gas chromatography and calibrated using the correction factors of formulated standards.
[0375] The conversion and selectivity were calculated based on the molar content of each component in the reaction solution, and the calculation method was the same as that described in Test Example I-2.
[0376] [Table 13]
[0377] As can be seen from the above table, catalysts D-IV-1 to D-IV-3 exhibit lower conversion rates under the same process conditions and lower activity than catalysts C-IV-1 to C-IV-13 of the present application; compared with catalysts C-IV-1 to C-IV-13, catalysts D-IV-1 to D-IV-3 have lower selectivity for hexanediamine but higher selectivity for other components, indicating that the reaction materials are not easily desorbed from catalysts D-IV-1 to D-IV-3 and therefore undergo further reactions to produce other by-products.
[0378] Test Example IV-3 This test example illustrates a process for producing ethylamine by hydroamination of ethanol using a catalyst according to a fourth type of embodiment of the present application.
[0379] 100 mL of catalyst C-IV-3 obtained in Example IV-3 was measured and placed in a fixed-bed reactor. It was activated using hydrogen at 220°C for 2 hours, then cooled to 173°C, and the system pressure was increased to 1.65 MPa using hydrogen. Ammonia was then metered into the reaction system via a metering pump, preheated to 110°C, and sent to the top of the reactor. Ethanol was then fed to the top of the reactor via a metering pump, and hydrogen was steadily introduced via a gas mass flow meter. The molar ratio of hydrogen, ammonia, and ethanol was 3:5:1, and the liquid phase volumetric space velocity of ethanol was 0.5 hr. -1 The catalytic amination reaction was carried out in a reactor at a reaction temperature of 178°C and a reaction pressure of 1.6 MPa. After the reaction stabilized, the reaction solution was sampled and analyzed (the analytical conditions and the calculation methods for conversion and selectivity were the same as those in Test Example IV-2). The analytical results are shown in Table IV-3.
[0380] [Table 14]
[0381] Test Example IV-4 Catalysts C-IV-2, C-IV-9, D-IV-1, D-IV-2, and D-IV-3 were placed in a fixed-bed reactor under the same conditions as in Test Example IV-2, except that the reaction time was extended. Tests were conducted for 500 hours. The reaction solution at 20 hours of reaction time (analysis conditions and calculation methods for conversion and selectivity were the same as in Test Example IV-2) and after 500 hours of reaction (analysis conditions and calculation methods for conversion and selectivity were the same as in Test Example IV-2) were analyzed and compared. The analytical results are shown in Table IV-4.
[0382] [Table 15]
[0383] After 500 hours of evaluation, the activity and selectivity of catalysts C-IV-2 and C-IV-9 remained essentially unchanged, while the activity and selectivity of comparative catalysts D-IV-1, D-IV-2, and D-IV-3 clearly decreased. The specific surface area, pore volume, and carbon deposition of each catalyst were characterized, and it was found that the specific surface area and pore volume of catalysts D-IV-1, D-IV-2, and D-IV-3 decreased significantly, while the specific surface area and pore volume of catalysts C-IV-2 and C-IV-9 remained essentially unchanged (decreased by less than 2%), and the carbon deposition of catalysts D-IV-1, D-IV-2, and D-IV-3 was more than twice that of catalysts C-IV-2 and C-IV-9.
[0384] Test Example IV-5 This example illustrates a process for producing hexanediamine from a mixture of 1,6-hexanediol, hexamethyleneimine, and aminohexanol using a catalyst according to a fourth type of embodiment of the present application.
[0385] 100 mL of catalyst C-IV-3 obtained in Example IV-3 was weighed and placed in a fixed-bed reactor. It was activated with hydrogen at 220°C for 2 hours, then cooled to 175°C, and the system pressure was increased to 14 MPa with hydrogen. Ammonia was then metered into the reaction system via a metering pump, preheated to 150°C, and sent to the top of the reactor. A mixed solution containing 53 wt% 1,6-hexanediol, 30 wt% hexamethyleneimine, and 17 wt% 6-amino-1-hexanol was fed to the top of the reactor via a metering pump, and hydrogen was steadily introduced via a gas mass flow meter. The molar ratio of hydrogen to ammonia to the total amount of the three substances in the mixed solution was 3:10:1, and the liquid phase volumetric space velocity of the mixed solution was 0.5 h / min. -1 The catalytic amination reaction was carried out in a reactor at a reaction temperature of 180°C and a reaction pressure of 14 MPa. After the reaction stabilized, the reaction solution was sampled and analyzed (the analytical conditions and the calculation methods for conversion and selectivity were the same as those in Test Example IV-2). The analytical results are shown in Table IV-5.
[0386] [Table 16]
[0387] Although the present application has been described in detail above with reference to preferred embodiments, it is not intended to be limited to these embodiments. Various modifications can be made in accordance with the inventive concept of the present application, and these modifications are within the scope of the present application.
[0388] It should be noted that the various technical features described in the foregoing embodiments can be combined in any suitable manner without contradiction, and in order to avoid unnecessary repetition, the present application does not describe various possible combinations, but such combinations also fall within the scope of the present application.
[0389] Furthermore, various embodiments of the present application can be combined in any manner without departing from the spirit of the present application, and such combined embodiments should be considered as part of the disclosure of the present application.
Claims
1. 1. A catalyst useful for producing organic amines by catalytic amination, comprising: The catalyst comprises an inorganic porous carrier containing aluminum and / or silicon, and an active metal component supported on the carrier, the active metal component comprises at least one metal selected from cobalt, nickel, or a combination thereof; the carrier has an L acid content of 85% or more relative to the total of the L acid content and the B acid content, the ratio of the L acid content of the carrier to the total of the L acid content and the B acid content being measured by pyridine probe adsorption analysis; The support comprises a matrix and a doping element, wherein the matrix is selected from alumina, silica, molecular sieve, diatomaceous earth, aluminosilicate, or a combination thereof; and A catalyst wherein said doping element is selected from the group consisting of Group IIIA non-metallic elements, Group VA non-metallic elements, Group VIA non-metallic elements, Group VIIA non-metallic elements, and combinations thereof, excluding chlorine.
2. The doping element is selected from boron, fluorine, phosphorus, sulfur, selenium, or a combination thereof; 2. The catalyst of claim 1, wherein the doping element in the support is derived from a non-metal acid radical ion, and the non-metal acid radical ion is selected from the group consisting of borate ions, fluoride ions, phosphate ions, sulfate ions, selenate ions, and combinations thereof.
3. 3. The catalyst of claim 1 or 2, wherein the support has at least one of the following characteristics: The ratio of the pore volume of pores having a pore diameter in the range of 7 to 27 nm to the pore volume of the support is 70 to 90%, and the ratio of the pore volume of pores having a pore diameter of less than 7 nm to the pore volume of the support is 0 to 10%; The support has an ammonia adsorption capacity of 0.3 to 0.6 mmol / g; The content of alumina in the support is 75 wt. % or more based on the total amount of the matrix; the content of the doping element is 0.07 to 4% by weight, relative to the total amount of the matrix; The carrier is 100 to 220 m 2 / g specific surface area; The support has a pore volume of 0.4 to 1.1 ml / g; and The isoelectric point of the carrier is 3.5 to 5.
5.
4. 4. The catalyst of claim 1, wherein the active metal component is present in an amount of 15 to 37 g per 100 g of the matrix, and the active metal component has a particle size of 3 to 8 nm.
5. further comprising a metal promoter supported on the support, wherein the metal promoter comprises at least one metal selected from Cr, Mo, W, Mn, Re, Cu, Ag, Au, Zn, La, and Ce; 5. The catalyst of any one of claims 1 to 4, wherein the metal promoter is present in an amount of 0.5 to 8 g per 100 g of the matrix.
6. or alternatively, the metal co-catalyst comprises a combination of at least one Group VIIB metal and at least one Group IB metal, wherein the weight ratio of the Group VIIB metal to the Group IB metal, calculated as elemental metals, is from 0.05 to 15:1; or alternatively, or alternatively, the metal co-catalyst comprises a combination of at least one Group VIIB metal and at least one Group IIB metal, wherein the weight ratio of the Group VIIB metal to the Group IIB metal, calculated as elemental metals, is from 0.2 to 20:1; or alternatively, the metal co-catalyst comprises a combination of at least one Group VIB metal, at least one Group IB metal, and at least one Group IIB metal, wherein the weight ratio of the Group VIB metal to the Group IB metal to the Group IIB metal, calculated as elemental metals, is 0.2-8:0.2-8:1; 6. The catalyst of claim 5, wherein the Group VIIB metal is selected from manganese, rhenium, or a combination thereof; the Group IB metal is selected from copper, silver, gold, or a combination thereof; the Group IB metal is zinc; and / or the Group VIB metal is selected from molybdenum, tungsten, or a combination thereof.
7. further comprising a metal promoter supported on said support, said metal promoter being a combination of at least one Group IIA metal, at least one Group IIB metal, and at least one Group VA metal; the metal promoter is present in an amount of 0.1 to 10 g per 100 g of the matrix; the weight ratio of the Group IIA metal to the Group IIB metal to the Group VA metal in the metal cocatalyst is 0.1-10:0.1-10:1; 5. The catalyst of any one of claims 1 to 4, wherein the Group IIA metal is selected from magnesium, calcium, barium, or a combination thereof, the Group IIB metal is zinc, and / or the Group VA metal is bismuth.
8. A method for producing the catalyst according to any one of claims 1 to 7, comprising the following steps 1) to 3): 1) providing an inorganic porous support containing aluminum and / or silicon, the support being obtained by successively shaping, drying and calcining a mixture containing a doping element and a matrix or a precursor thereof, the calcination conditions including a temperature of 800 to 1050°C and a calcination time of 2 to 20 hours, the support having an L acid content of 85% or more relative to the total of the L acid content and the B acid content; 2) supporting the active metal component and, optionally, a metal promoter on the support, wherein the metal promoter comprises at least one metal selected from Cr, Mo, W, Mn, Re, Cu, Ag, Au, Zn, La, and Ce; and 3) subjecting the material obtained in step 2) to a heat treatment and optionally a reduction treatment to obtain said catalyst; The heat treatment comprises calcining or a combination of drying and calcining.
9. The method of claim 8, wherein the matrix is selected from alumina, silica, molecular sieve, diatomaceous earth, aluminosilicate, or a combination thereof; the doping element is selected from the group consisting of Group IIIA non-metallic elements, Group VA non-metallic elements, Group VIA non-metallic elements, Group VIIA non-metallic elements, and combinations thereof, excluding chlorine; 9. The method of claim 8, wherein the drying conditions in step 1) include a temperature of 80 to 150°C and a drying time of 6 to 20 hours.
10. The method of claim 9, wherein the doping element is selected from boron, fluorine, phosphorus, sulfur, selenium or a combination thereof.
11. 10. The method of claim 9, wherein the doping element is provided using a carrier modifier comprising at least one compound capable of providing a non-metallic acid radical ion, the non-metallic acid radical ion being selected from borate ions, fluoride ions, phosphate ions, sulfate ions, selenate ions, or combinations thereof.
12. 12. The method of any one of claims 8 to 11, wherein the supporting step of step 2) comprises impregnating the support with a solution comprising a precursor of the active metal component and, optionally, a precursor of the metal promoter.
13. For an amination reaction, the method comprises contacting an amination raw material and an aminating agent with the catalyst according to any one of claims 1 to 7 in the presence of hydrogen to obtain an organic amine; the amination feedstock is selected from a C2 to C20 alcohol, a C3 to C20 ketone, a C2 to C20 alcohol amine, a C2 to C20 aldehyde, or a combination thereof; 1. A process for producing an organic amine, wherein the aminating agent is selected from ammonia, a C1-C12 primary amine, a C1-C12 secondary amine, or a combination thereof.
14. The amination conditions are as follows: a molar ratio of hydrogen to the aminating agent to the aminating raw material is 1 to 6:2 to 35:1; a temperature is 110 to 210°C; a pressure is 1 to 17 MPa; and a liquid phase volumetric space velocity of the aminating raw material is 0.06 to 1 m 3 / (m 3 The process of claim 13, comprising: h).
15. When the amination raw material is a monohydric alcohol, the amination conditions are a molar ratio of hydrogen to the aminating agent to the amination raw material of 1 to 4:2 to 8:1, a temperature of 130 to 210°C, a pressure of 0.8 to 3.5 MPa, and a liquid phase volumetric space velocity of the amination raw material of 0.1 to 0.8 m 3 / (m 3 h) including When the amination raw material is a ketone or an aldehyde, the amination conditions are a molar ratio of hydrogen to the aminating agent to the amination raw material of 1 to 4:2 to 5:1, a temperature of 105 to 180°C, a pressure of 0.7 to 2.5 MPa, and a liquid phase volumetric space velocity of the amination raw material of 0.1 to 1 m 3 / (m 3 h) including When the amination raw material is an alcohol amine, the amination conditions are a molar ratio of hydrogen to the aminating agent to the amination raw material of 1 to 4:3 to 20:1, a temperature of 130 to 200°C, a pressure of 1 to 16 MPa, and a liquid phase volumetric space velocity of the amination raw material of 0.06 to 0.8 m 3 / (m 3 h) including When the amination raw material is a dihydric alcohol, the amination conditions are a molar ratio of hydrogen to the aminating agent to the amination raw material of 1 to 4:3 to 33:1, a temperature of 130 to 230°C, a pressure of 1 to 25 MPa, and a liquid phase volumetric space velocity of the amination raw material of 0.1 to 0.9 m 3 / (m 3 15. The process of claim 14, comprising: h).
Citation Information
Patent Citations
Catalyst and its preparation method and application, and method for preparing ethanediamine through ethylene glycol hydrogenation amination
CN106607060A
Catalyst for synthesizing hexamethylenediamine
CN111151256A